Systems and methods for continuous production of fibrous materials and nanoparticles
The nanofiber group is converted into single nanoparticles and dispersed into the substrate through a continuous manufacturing system, which solves the problems of low efficiency of the filter media and uneven dispersion of nanoparticles in the prior art, and improves the filtration efficiency and life of the filter media.
Patent Information
- Application Number
- CN202380041729.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-08
- Filing Date
- 2023-04-07
- Publication Date
- 2024-12-31
AI Technical Summary
Existing filter media are inefficient in capturing submicron particles, uneven dispersion of nanoparticles leads to degradation of filtration performance, and wet lamination methods fail to successfully integrate nanoparticles uniformly into the entire nonwoven material.
Using a continuous manufacturing system, the nanofiber groups are converted into single nanoparticles and evenly dispersed into the substrate through a dispersion device to form fiber materials with a larger nanoparticle surface density, improving filtration efficiency and life.
It improves the filtration efficiency and life of the filter media, enhances the ability to capture submicron pollutants, extends the service life of the filter, and achieves uniform dispersion of nanoparticles in the material.
Smart Images

Figure BDA0005143701940000411 
Figure BDA0005143701940000421 
Figure BDA0005143701940000441
Abstract
Description
[0001] Citation to Related Applications
[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 329,137, filed April 8, 2022, the entire disclosure of which is incorporated herein by reference for all purposes. This application is also related to commonly assigned, co-pending U.S. Provisional Patent Application Nos. 63 / 329,009, 63 / 328,983, 63 / 328,998, 63 / 328,970, 63 / 328,959, 63 / 329,146, 63 / 329,018, 63 / 329,155, 63 / 329,158, 63 / 329,161, and 63 / 329,162, all of which were filed on April 8, 2022, the entire disclosures of which are incorporated herein by reference for all purposes. Technical Field
[0003] The present specification generally relates to a system and method for continuously producing a material comprising fibers and nanoparticles and articles comprising such a material. Background Art
[0004] Due to their fine fiber size, fibrous materials are particularly useful for capturing contaminants in filtration devices. The fibers of the filter media are measured in microns and can be formed by spunbonding, meltblowing, electrospinning or other techniques. When fluid flows through the filter media, the fine fibers capture and retain contaminants in the filter media.
[0005] The two main types of filtration devices that incorporate fiber materials include surface filters and depth filters. Surface filters, such as membranes or films, act as a barrier to contaminants that are captured before they enter the media structure. These surface filters typically have submicron pore sizes and narrow pore size distributions. Surface filters tend to have higher particle capture efficiencies. However, they also have higher pressure drops and low dust loading capacities. High pressure drops result in reduced airflow through the filter. Low dust loading capacities significantly reduce filter life. As a result, surface filters have a limited number of applications in the air filtration industry.
[0006] Depth filters are commonly used in air filtration devices with medium to high efficiency, low pressure drop, and high dust loading capacity. Conventional home and commercial air filters such as HEPA filters are usually rated based on the filter's ability to capture particles of approximately 0.3 to 10 microns. This rating is called the Minimum Efficiency Reporting Value (MEMV) or MERV, which is established by the American Society of Heating, Refrigerating and Air Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher values indicating a higher efficiency in capturing a particular type of particle.
[0007] Contaminants come in a wide range of sizes. However, contaminants smaller than 1 micron are the most harmful particles to the human body and are more difficult to filter out. For example, conventional mechanical air filters typically report a MERV rating of approximately 8-10 for fiber filter materials. Therefore, these filter media are generally unable to capture submicron particles, such as viruses and other harmful pathogens.
[0008] The filtration industry focuses on two different methods of capturing these submicron particles: electrostatic forces and the use of nanoparticles in the filter media. Electrostatic filters are formed by electrostatically charging the fibers within the fibrous material using tribocharging methods, corona discharge, hydrogen charging, electrostatic fiber spinning, or other known methods. Electrostatic filters are most effective at capturing submicron particles, fairly effective at capturing particles between 1 and 3 microns in size, and least effective at capturing larger particles between 3 and 10 microns. Electrostatic fibers are commonly used in many filtration applications such as face masks and high efficiency filters to filter submicron contaminants such as viruses and other contaminants.
[0009] One disadvantage of electrostatic filters is that the static charge decays over time and with filter use. As a result, the filter's efficiency decreases more quickly, shortening its life. For example, an electrostatic filter with an initial MERV rating of 13 may lose at least 2-3 points of MERV rating after the electrostatic force decays. This compromises the integrity of the filter and may partially or completely inhibit its ability to capture submicron particles.
[0010] Another approach to capturing submicron contaminants is to use nanoparticles in combination with fibers. A filtration system may employ a filter media containing larger fibers with diameters measured in microns and relatively small nanoparticles. The nanoparticles increase the surface area in the media for capturing particles by reducing the overall fiber size in the media. Nanoparticles also tend to huddle against each other, increasing the packing density within the filter media. It has been shown that even a small layer of nano-sized fibers on a microfiber material can improve the material's filtration characteristics.
[0011] The most common method of incorporating nanoparticles into filter media is to apply a thin layer of continuous nanofibers on a nonwoven substrate by electrospinning. The nanoparticles generally extend parallel or perpendicular to the surface of the main filter media layer and provide efficient filtration of small particles in addition to the filtration of larger particles provided by the coarse filter media. For example, U.S. Pat. No. 6,743,273 discloses a filter media in which a continuous nanofiber layer is deposited on the surface of the substrate. U.S. Pat. No. 10,799,820 also discloses an air filter media comprising a continuous nanofiber layer on the surface of the filter media.
[0012] Although existing filter media incorporating nanoparticles have improved the relative efficiency of these filters, the commercial potential of these filters is limited in certain applications because the nanoparticles are typically dispersed onto the surface of the fiber material. A thin layer of nanoparticles on the filter surface provides only limited particle filtration and has a low dust holding capacity.
[0013] Although there have been many attempts to incorporate nanomaterials into filter media to improve overall filtration efficiency, these attempts are limited to so-called "wet-laid" methods. These wet-laid methods involve incorporating chopped nanofibers into a liquid slurry to separate entangled nanofibers with the help of a surfactant. For example, U.S. Patent No. 10,252,201 discloses a filter medium made of a mixture of chopped nanofibers and chopped coarse fibers formed by a wet-laid method. Similarly, U.S. Patent Application No. 2021 / 0023813 discloses a method for manufacturing a composite structure consisting of a continuous fiber nonwoven substrate with discontinuous fibers (e.g., carbon nanofibers). The method includes pulling a continuous fiber nonwoven substrate through a slurry of discontinuous fibers, wherein the nanomaterial is embedded in the nonwoven substrate.
[0014] While these structures have demonstrated improved efficiency, they suffer from other issues such as reduced life and / or efficiency when the media is placed under normal use conditions. Additionally, these wet-laid processes have not been successful in incorporating the nanoparticles uniformly throughout the nonwoven material, which results in agglomeration of the nanoparticles within the material, further reducing its efficiency and overall dust collection capabilities.
[0015] Therefore, there is a need for an improved system and method for the continuous manufacture of fibrous materials and articles (eg, filters) containing such materials. It is particularly desirable to incorporate nanoparticles throughout the material to improve the performance characteristics of the article. Summary of the invention
[0016] The following is a brief summary of the claimed subject matter to provide a basic understanding of some aspects of the claimed subject matter. This summary is not an extensive overview of the claimed subject matter. It is not intended to identify key or critical elements of the claimed subject matter or to define the scope of the claimed subject matter. Its sole purpose is to present some concepts of the claimed subject matter in a concise form as a prelude to the more detailed description presented later.
[0017] The present disclosure provides a system and method for continuously manufacturing fiber materials and articles containing such materials. The material may include a substrate, such as a sheet, layer, film, porous film, net, screen or other medium. The article contains fibers and contains nanoparticles bonded to the fibers and incorporated into at least a portion of the article.
[0018] In one aspect, a system includes a conveyor for continuously advancing a substrate containing a fiber material from an upstream end to a downstream end, and a feeder for feeding a nanofiber group into a fluid medium. A fiberizing device is coupled to the feeder and is configured to convert the nanofiber group into individual nanoparticles. A dispersing device is coupled to the fiberizing device for dispersing the nanoparticles into the substrate to form a material. The system continuously manufactures the material to form a product with improved quality, output, and reduced cost and time. In addition, the system can be scalable and can manufacture products with less changes.
[0019] In an embodiment, the system is configured to continuously disperse the nanoparticles into the substrate at a rate or add-on of about 0.1 g / m2 to about 20 g / m2, preferably at least about 2.0 g / m2. This provides a fibrous material with a greater nanoparticle surface density (grams / square meter (gsm)) or "add-on" within the material. The term "add-on" is used herein to refer to the surface density (gsm) of a material, fiber, or particle in a thin layer, sheet, or film of the material.
[0020] In certain embodiments, the articles are filter media and filters, such as air filters, masks, gas turbine and compressor intake filters, and panel filters, etc. Providing a greater amount of nanoparticles added to the filter in a continuous process increases the total surface area within the filter media, which improves its filtration efficiency and allows the capture of submicron pollutants without significantly compromising other factors, such as the pressure drop (i.e., airflow) through the filter. In addition, filters manufactured using the continuous process described herein are able to withstand rigorous regulation, which allows the filter to achieve the same level of filtration performance throughout its life.
[0021] In some embodiments, nanoparticles are "deeply" dispersed in substrate. As used herein, the term "deeply" refers to a dispersion range of nanoparticles that exceeds the first surface of substrate, so that at least some nanoparticles are located between the first surface and the second relative surface in the internal structure of substrate or medium. In some embodiments, nanoparticles are dispersed in substantially the entire medium from the first surface to the relative second surface. In other embodiments, nanoparticles are dispersed to the position between the first surface and the second surface through a portion of the medium from the first surface. In other embodiments, nanoparticles are arranged with a density gradient from the first surface of substrate to the relative second surface. The density of nanoparticles can be larger at the first surface or second surface.
[0022] The system may also include a negative pressure source or vacuum source, which is arranged below the substrate relative to the dispersion device to increase the penetration depth and uniformity of the nanoparticles. The negative pressure source can be any suitable suction device that sucks the nanoparticles through the substrate, such as a suction pump or the like.
[0023] In some embodiments, the material may include a nonwoven material. The nonwoven material discussed herein may include any substrate, such as a sheet, layer, film, perforated membrane, net, mesh or other medium, which comprises the structure of individual fibers or threads interwoven with each other. The example of suitable nonwoven material includes but is not limited to fibers, layers or nets processed through meltblowing, spunbonding, bonding combing, air-laid, co-molding and hydraulic entanglement. In other embodiments, it is envisioned to adopt knitting or woven fabrics as substrate.
[0024] The fiberizing device is configured to transform (for example, open, separate and / or separate) clusters (clusters), bundles (clumps) or other groups of nanoparticles into single nanoparticles with at least one size less than 1 micron. Single nanoparticles can be produced in any suitable fluid medium. In some embodiments, the fluid medium is a gaseous medium, such as air, helium, nitrogen, oxygen, carbon dioxide and water vapor etc. In the gaseous medium, single nanoparticles are separated and then dispersed in the fiber stream so that the nanoparticles are more evenly distributed in the whole fiber material and / or the goods.
[0025] In certain embodiments, the feeder comprises a hopper or similar device configured to deliver nanofiber clusters, bundles, or other groups to a fiberizing device at a rate such that the nanofiber groups are converted into individual nanoparticles that are dispersed onto the substrate at an addition amount of at least about 2.0 g / m2. The nanofiber groups may be of any suitable size and may or may not be entangled with each other.
[0026] The fiberizing device may include a pump coupled to a hopper and a source of compressed air or other suitable fluid source coupled to the pump. The compressed air source provides a motive fluid to circulate the nanofibers throughout the system and ultimately outwardly into a suitable dispersing device. The pump may include any suitable pump, such as a volumetric pump, a centrifugal pump, and an axial flow pump, etc. In one embodiment, the pump includes an ejector configured to generate sufficient negative pressure to draw small clusters of nanofibers out of the separator and into the pump through the channel.
[0027] The pump is configured to push the nanofiber group through the gas medium against one or more surfaces in the fiberizing device or against the surface together with the gas medium with sufficient speed and / or momentum to open the nanofiber group and / or separate the nanofiber group into individual nanoparticles with at least one size less than 1 micron. The applicant has found that by advancing the nanofiber group into a suitable surface at a sufficient speed to generate the necessary kinetic energy to break and separate at least some of the nanofiber clusters in these nanofiber clusters into individual nanoparticles, it is possible to separate individual nanoparticles from the nanofiber group in the gas medium. In some embodiments, the speed of the nanoparticles is about 500 feet per minute (fpm) to about 10,000 fpm, preferably about 2,000 fpm to about 6,000 fpm.
[0028] The system can also include an energy source, such as a second pump, which is coupled to the first pump and is configured to push small clusters of nanofibers from the first pump to the surface at a sufficient speed to break up the nanofibers and convert small clusters of at least some nanofibers into single nanoparticles. The surface can be any surface that hinders the nanofibers from flowing through the channel, such as the inner wall of the channel at the junction, or other changes in the direction of the inner wall, such as a curved surface or a vertical surface, etc. Alternatively, the channel can include a wall or other surface that is arranged in the channel or protrudes into the channel in the fluid path. In one embodiment, the channel extends to a roughly T-shaped joint, which includes two independent channels extending from the joint. The second pump is configured to advance the nanofibers into the wall of the T-joint at a speed that is enough to split at least some nanofibers.
[0029] In some embodiments, the system further comprises one or more reactors for separating single nanoparticles that have been separated from the nanofiber groups that have not been completely broken up. The reactor comprises a housing coupled to the channel and having an internal chamber and a negative pressure source, the negative pressure source being configured to suck away smaller nanofiber clusters from the single nanoparticles.
[0030] In an embodiment, each reactor comprises a rod or cylinder substantially located at the center and one or more inlets at one end of the inner chamber and substantially around the center rod. The inlet is coupled to the passage so that the nanofiber clusters and single nanoparticles are sucked into the chamber through the inlet. The center rod comprises an opening at the end opposite to the inlet. The opening is coupled to the inner passage in the center rod and has an outlet coupled to a nozzle or other dispersing device. This allows nanoparticles to enter the reactor through the inlet, then enter the center rod, and arrive at the dispersing device.
[0031] The inlet can be in an angled orientation relative to the center bar so that nanofibers and nanoparticles enter the inner chamber at a transverse angle relative to the outer surface of the reactor. In a preferred embodiment, the orientation of at least one or more inlets makes them move along a direction substantially tangent to the center bar when nanofibers and nanoparticles enter the reactor. After they enter the annular chamber around the rod, the velocity vector (speed and direction) of nanofibers and nanoparticles produces eddy currents in the reactor so that they swirl around the center bar from one end to the other. Because a single nanoparticle is much lighter than the entangled nanofibers that still gather together, a single nanoparticle is sucked into the inlet of the center bar. When nanofiber clusters pass through the reactor, the eddy currents in the chamber can also further break up (e.g., open, separate and / or individualize) nanofiber clusters.
[0032] Reactor can also comprise one or more outlets at the opposite end of inlet.The larger and heavier nanofiber clusters that have not yet been broken are extracted through these outlets.Therefore, the nanoparticles of separation and individualization are sucked into the nozzle, and the nanofiber clusters are extracted through the outlet.These outlets can be coupled to the first pump or the second pump, or coupled to other pumps in the system, and these other pumps are designed to further break up the nanofiber clusters and recirculate them back into the reactor.
[0033] The system can also include a coating device for dispersing a binder on the fiber in the substrate. The binder can include multiple conventional materials, including natural materials (such as starch, dextrin, guar gum, etc.) or synthetic resins (such as EVA, PVA, PVOH, SBR and polyglycolide, etc.). In some embodiments, the substrate includes its own binder composition. In these embodiments, the substrate may be added or not added with a binder or bonding material. In such an embodiment, the substrate includes biocomponent fiber, and one of the components includes an outer sheath that at least partially surrounds an inner core.
[0034] Described coating device can comprise any suitable device that binding agent is dispersed into whole base material.In one embodiment, described coating device comprises spraying device, and this spraying device has the upstream end of adjacent feeder and the outlet of nozzle.This sprayer can be positioned at the downstream of fibrosis device, thereby can spray binding agent after nanoparticle deposition.In other embodiments, described system can comprise two sprayers: a sprayer is positioned at the upstream of fibrosis device, and second sprayer is positioned at the downstream of fibrosis system, is used for coating base material with the second binding agent after depositing nanoparticle.
[0035] The second device may further include a dryer, such as an infrared oven, etc., which is arranged near the downstream end of the feeder and is used to heat the nanoparticles and the fibers to bond the nanoparticles to the fibers in the substrate.
[0036] In another aspect, a process for continuously manufacturing a fiber material includes continuously advancing a substrate containing the fiber material from an upstream end to a downstream end, and feeding a nanofiber group into a fluid medium. The nanofiber group is converted into nanoparticles in the fluid medium and then dispersed into the substrate between the upstream end and the downstream end, thereby forming the fiber material.
[0037] In certain embodiments, the nanoparticles are dispersed into the substrate at a rate or addition of about 0.1 g / m2 to about 20 g / m2, preferably at least about 2.0 g / m2. The substrate may be advanced at a speed of about 0.05 to 1.0 m / s.
[0038] In certain embodiments, the nanofiber population and nanoparticles are propelled in the fluid medium at a velocity of about 500 to about 10,000 feet per minute (fpm), preferably about 2,000 fpm to about 6,000 fpm.
[0039] Nanoparticles are dispersed on the first surface of substrate so that nanoparticles penetrate at least the first surface of substrate. In some embodiments, nanoparticles are sprayed or dispersed on the first surface of substrate, and suction is applied on the second surface of substrate relative to the first surface to draw single nanoparticles through substrate. In some embodiments, nanoparticles are dispersed in at least about 25% thickness or at least about 50% thickness range through the surface in substrate. Nanoparticles can be incorporated into substantially the entire substrate from the first surface to the relative second surface. Nanoparticles can form a density gradient from the outer surface of substrate to the middle portion or relative second surface.
[0040] Described process can also comprise that adhesive is applied on the fibrous material in substrate.For example, adhesive can be sprayed on substrate before and / or after nanoparticle is dispersed in substrate.Adhesive stops nanoparticle from directly passing substrate, and when nanoparticle is attached to adhesive, can improve uniformity and the penetration of nanoparticle in the internal structure of substrate.
[0041] In certain embodiments, the nanofiber group is drawn into a stream of compressed air and is propelled toward a surface to break at least a portion of the nanofiber clusters into individual nanoparticles. The surface may be, for example, the inner wall of the channel at the junction, or other changes in direction along the inner wall, such as a curved surface or a vertical surface, etc. In one embodiment, the nanofibers are propelled to a substantially T-shaped joint that includes two separate channels extending therefrom.
[0042] In some embodiments, the method also includes separating the single nanoparticle separated from the nanofiber bundle that has not yet been completely broken. In these embodiments, particles (nanofiber clusters and single nanoparticles) are driven into the inner chamber of one or more reactors. Particles are separated in the reactor, so that the nanoparticles enter the nozzle, and the remaining nanofiber clusters leave the reactor to recirculate in the system. In a preferred embodiment, particles are advanced into the reactor at an angle to the center bar so that the velocity vectors (speed and direction) of nanofibers and nanoparticles produce eddy currents in the reactor, making them swirl from one end to the other around the center bar. Because single nanoparticles are much lighter than the entangled nanofibers that are still gathered together, single nanoparticles are sucked into the entrance of the center bar. When nanofiber clusters pass through the reactor, the eddy currents in the chamber can further break up (e.g., open, separate and / or individualize) nanofiber clusters.
[0043] The recitation herein of desirable objectives met by various embodiments of this specification is not meant to imply or suggest that any or all of these objectives are present as essential features, either individually or collectively, in the most general embodiment of this specification or in any of its more specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a side view of a fiber material with nanoparticles dispersed throughout a portion of the material;
[0045] Figure 2 is a side view of a fiber material with nanoparticles dispersed throughout the material;
[0046] Figure 3 is a side view of a fiber material with nanoparticles dispersed throughout the material in a gradient manner;
[0047] Figure 4 A double layer of filter media is shown;
[0048] Figures 5A-5C Biocomponent fibers incorporated into a fibrous material are shown;
[0049] Figure 6 A pleated fiber filter media is shown;
[0050] Figure 7 A representative air filter is shown;
[0051] Figure 8 A gas filter having a first support membrane layer and a second support membrane layer and a filter medium is shown;
[0052] Fig.9A and 9B A porous membrane used as a supporting membrane layer is shown;
[0053] Figures 10A-10E Various embodiments of porous membranes with nanoparticles incorporated into the membrane are shown;
[0054] Fig.11 A gas filter is shown;
[0055] Fig.12 A system for manufacturing a fibrous material within a substrate is schematically shown;
[0056] Fig.13 A system for converting nanofiber clusters into individual nanoparticles is schematically shown;
[0057] Figures 14A-14C The photos are large clusters of nanofibers, smaller clusters of nanofibers, and individual nanoparticles, respectively;
[0058] Fig.15Shows Fig.13 The system's injectors;
[0059] Fig.16 Shows Fig.13 A reactor of the system;
[0060] Fig.17 Another embodiment of a system for converting nanofiber clusters into individual nanoparticles is shown;
[0061] Fig.18 A system for making a double-layer fiber material is shown;
[0062] Fig.19 A fiber material showing the dispersion of nanoparticles within a certain depth of the material;
[0063] Fig. 20 A fiber material showing nanoparticles dispersed throughout the depth of the material and a scrim layer covering the nanoparticles;
[0064] Fig.21 A double layer fiber material is shown with nanoparticles dispersed on the inner surfaces of both layers; and
[0065] Fig. 22 An alternative embodiment of a system for producing a fibrous material in a fluid stream is shown;
[0066] Fig.23A This is a photo of a fiber material without the use of a binder;
[0067] Fig. 23B It is a photograph of a fiber material with a binder;
[0068] Fig.24A is a photograph of a fibrous material in which the nanoparticles are dispersed throughout the material in bundles or clusters; and
[0069] Fig. 24B is a photograph of a fiber material with nanoparticles dispersed substantially uniformly throughout the material. DETAILED DESCRIPTION
[0070] This specification and the accompanying drawings illustrate exemplary embodiments and should not be considered restrictive, and the claims (including equivalents) define the scope of this specification. Various mechanical, compositional, structural and operational changes can be made without departing from the spirit and scope of this specification and the claims (including equivalents). In some cases, well-known structures and techniques are not shown or described in detail to avoid confusing the description. The same numbers in two or more drawings represent the same or similar elements. In addition, whenever feasible, the elements and related aspects described in detail with reference to one embodiment can be included in other embodiments that do not specifically show or describe them. For example, if a certain element is described in detail with reference to one embodiment without describing the element with reference to a second embodiment, the element can still be included in the second embodiment. In addition, the description herein is for illustrative purposes only and does not necessarily reflect the actual shape, size or dimensions of the system or the components shown.
[0071] It should be noted that the singular forms "a," "an," and "the," as well as any singular use of any word as used in this specification and the appended claims, include plural referents unless expressly and unequivocally limited to one referent. The term "include," and its grammatical variations as used herein are intended to be non-limiting, such that the recitation of items in a list does not exclude other like items that can be substituted or added to the listed items.
[0072] Unless otherwise indicated, any numerical values are approximate, whether or not the term "about" or "approximately" is used. The materials, methods, and examples described herein are illustrative only and not limiting.
[0073] The present disclosure provides a system and method for continuously manufacturing fiber materials and products comprising such materials. The material may include a substrate, such as a sheet, layer, film, porous membrane, net, silk screen or other medium. The product comprises fibers, and comprises nanoparticles that are bonded to the fibers and incorporated into at least a portion of the product. The term "nanoparticle" as used herein refers to any particle having a size less than 1 micron on at least one axis or dimension. For example, a fiber having a diameter or width less than 1 micron and a length greater than 1 micron is a nanoparticle as used herein.
[0074] In some embodiments, each individual nanoparticle can be a small particle with a size in the range of about 1 nanometer to about 1000 nanometers, preferably in the range of about 1 nanometer to about 650 nanometers. The particle size of at least half of the particles in the number size distribution can be 100 nanometers or less. Most nanoparticles are usually composed of only hundreds of atoms. When the size of nanoparticles approaches the atomic scale, the material properties will change. This is because the surface area to volume ratio increases, which causes the surface atoms of the material to dominate the performance of the material. Due to its very small size, when compared with bulk materials such as powders, plates, sheets or larger fibers, nanoparticles have a very large surface area to volume ratio. This characteristic makes nanoparticles have unexpected optical, physical and chemical properties, because they are small enough to limit their electrons and produce quantum effects.
[0075] In some embodiments, the nanoparticles include nanofibers having at least one dimension (i.e., diameter, width, or height, etc., depending on the cross-sectional shape of the fiber) less than 1 micron. The nanofibers may have continuous lengths, or the nanofibers may have discrete lengths, such as 1 to 100,000 microns, preferably about 100 to 10,000 microns.
[0076] In some embodiments, substrate comprises nonwoven material, and it comprises the structure of individual fiber or thread-like thing that is interwoven, interlocked or bonded together.Nonwoven fabric can comprise sheet or web structure that is combined by mechanical, thermal or chemical mode winding fiber or filament (and by the mode of perforating film).They can be the substantially flat porous sheet made of individual fiber or molten plastic or plastic film directly.The example of suitable nonwoven material includes but is not limited to the fiber, layer or net processed by melt-blowing, spunbond or spunlace, thermal bonding, bonding combing, air-laid, wet-laid, co-molding, needle-punching, stitching or hydraulic entanglement.
[0077] In certain embodiments, the substrate may comprise knitted and / or woven materials. Knitted materials may include any knitting pattern suitable for a desired application. Knitted materials suitable for filter applications include weft knitting, warp knitting, knitted meshes, and compressed knitted meshes, etc. Woven materials suitable for filter applications include textile filter media, such as monofilament fabrics, multifilament fabrics, nylon nets, polyester nets, and polypropylene nets, etc. Woven textiles may be used, for example, for screen filter cloths, woven filter mats, and other punching parts, centrifugal filter bags, liquid filter bags, dust collector bags, dry bed bags, drum filters, filter belts, leaf filters, and rolled media, etc.
[0078] In some embodiments, nonwoven material can include the structure of short-cut fibers and / or filaments that are mixed or entangled. As used herein, short-cut fibers refer to fibers of limited length. Filaments used herein refer to fibers with substantially continuous length. In some embodiments, substrate can include short-cut coarse fibers, microfibers and / or fine fibers. As used herein, "fine fibers" refer to fibers with a diameter less than 1 micron, "coarse fibers" refer to fibers with a diameter greater than 10 microns, and microfibers refer to synthetic fibers with a diameter less than 10 microns.
[0079] In some embodiments, nanoparticles are dispersed "in depth" in substrates. As used herein, the term "in depth" refers to the dispersion of nanoparticles beyond the first surface of substrates, so that at least some nanoparticles are located between the first and second relative surfaces, into the internal structure of the substrate or medium. In some embodiments, nanoparticles are dispersed in substantially the entire medium from the first surface to the relative second surface. In other embodiments, nanoparticles are dispersed from the first surface through a portion of the medium to a position between the first surface and the second surface.
[0080] In some embodiments, the nanoparticles are spatially distributed three-dimensionally relative to the supporting fibers, which can increase the fiber surface area and the microvolume within the fibrous material. The three-dimensional distribution also provides resistance to complete clogging of specific portions of the fibrous material, which is particularly useful in filter media because it allows fluids (such as air and other gases) to pass through the filter, thereby reducing the overall pressure drop across the filter.
[0081] In other embodiments, the nanoparticles are arranged in a density gradient within the thickness of the substrate, so that the density of the nanoparticles is higher near a surface than near the relative surface, or the density of the nanoparticles is higher at the surface of the substrate than in the middle part. The density gradient shown in the accompanying drawings can be substantially linear, it can be reduced in a series of discontinuous steps, or the gradient can be random (that is, the reduction of density is not linear or step-wise). This density gradient provides many advantageous features (as described below) for some applications such as filters.
[0082] Nanoparticles can include any suitable material, such as glass, biosoluble glass, ceramic materials, acrylic, carbon, metals (e.g., alumina), polymers (e.g., nylon, polyethylene terephthalate, etc.), polyvinyl chloride (PVC), polyolefins, polyacetals, polyesters, cellulose ethers, polyalkylene sulfides, poly(arylene oxides), polysulfones, modified polysulfone polymers and polyvinyl alcohol, polyamides, polystyrene, polyacrylonitrile, polyvinylidene chloride, polymethyl methacrylate, polyvinylidene fluoride, and any combination thereof.
[0083] In some embodiments, the nanoparticles can be produced as bicomponent segmented pie and islands in the sea. The filaments are then stretched to obtain submicron filaments. The continuous filament nanofibers are cut according to the desired length, preferably from about 100 microns to about 10,000 microns.
[0084] In some embodiments, the nanoparticles are absorbents and adsorbents. In some embodiments, the nanoparticles are activated carbon fibers or activated carbon powders. In some embodiments, the nanoparticles are catalytic particles or catalytic fibers. In some embodiments, the nanoparticles can be obtained by feeding the submicron fiber nonwoven material into a pulverizer or crusher or trimmer, in which the bonded nonwoven material enters and the short-cut fibers come out. For example, a low-weight biocomponent meltblown or nano meltblown fabric can be fed into a pulverizer to obtain submicron nanoparticles.
[0085] In some embodiments, different nanoparticles can be mixed. For example, nanofibers and nanobeads can be mixed. Two different nanofibers with different melting points can also be mixed so that the nanoparticles with a lower melting point can act as a binder for the nanofibers with a higher melting point. Nanoparticles of different diameters and different lengths can also be mixed.
[0086] In some embodiments, the nanoparticles are selected from environmentally sustainable raw materials. The nanoparticles may include biosoluble glass nanofibers, biodegradable nanoparticles, compostable nanoparticles, or recyclable compositions.
[0087] Different types of nanoparticles can be combined. Some nanoparticles can be functional nanoparticles. For example, the functional nanoparticles can contain activated carbon and / or antimicrobial materials deposited on and / or attached to the fibers in the fiber material. This can improve the gas absorption efficiency and sterilization effect of the fiber. In addition, fiber products in which microfibers of glass and carbon nanoparticles are deposited can provide filtering and deodorization functions as filter media.
[0088] In some embodiments, nanoparticles are bonded to the fiber by mechanical entanglement. As discussed in more detail below, this mechanical bonding can be assisted by adhesives or bonding agents. In some embodiments, nanoparticles are not curled (that is, they do not include significant waves, bends, curls, coiled sawtooth or similar shapes associated with the nanoparticles in the relaxed state. In other embodiments, nanoparticles can have a curled body structure with discrete lengths. For example, when these curled nanofibers with discrete lengths are attached to the fiber, they entangle with each other, and are firmly attached to the fiber and around, thereby forming modified fibers. In other embodiments, the attachment of nanofibers to micron fibers is achieved by electrostatic charge attraction and / or van der Waals attraction between fiber and the nanoparticles.
[0089] A filter medium and filter are also provided, such as air filters, masks, gas turbine and compressor intake filters and plate filters, etc., which contain nanoparticles deeply dispersed in the filter medium. In some embodiments, the filter includes one or more support layers bonded to the filter medium. The support layer and / or the filter medium may include nanoparticles deeply dispersed in the layer. In some embodiments, a polymer layer, film layer or membrane is provided, which includes one or more orifices for gas or liquid to flow therethrough, and the nanoparticles are deeply arranged in the polymer layer. In other embodiments, the fiber material includes a flexible surface layer for a finger bandage pad or a mask, etc.
[0090] Provided herein is a system, apparatus and method for manufacturing fiber materials and articles (e.g., gas filters) containing fiber materials. Also provided is a system and method for separating single nanoparticles in a gas medium, such as air, helium, nitrogen, oxygen, carbon dioxide, etc. (not liquid), and the nanoparticles can be dispersed into another article, film, layer or substrate by air flow, aerosol, evaporator, spray or other appropriate delivery mechanism.
[0091] Although the following description is mainly given for fiber materials and filter media, it should be understood that the devices and methods disclosed herein are easily applicable to a variety of other applications. For example, the fiber materials disclosed herein can be used in household cleaning products, roof and floor products, automotive trim and headliners, reusable bags, wall coatings, filtration devices and insulation materials, etc. In addition, the individual nanoparticles separated and produced in the process described herein can be used in various coatings, composite materials and / or additives, such as polymers, food packaging, flame retardant materials, fuel cells, batteries, capacitors, nanoceramics, lamps, material manufacturing, manufacturing methods, reinforcement of composite materials, cement and other materials, medical diagnostic applications, medical treatment devices or therapies, tissue engineering (such as scaffolds for bone or tissue repair), drinking water, industrial process fluids, food and beverage products, drugs and biological preparations, tissue imaging, medical treatment delivery and environmental applications (such as biodegradable compounds), etc.
[0092] Figure 1 A nonwoven material or substrate 10 comprising a plurality of fibers 12 and nanoparticles 14 is shown. The substrate 10 has a first surface 16 and a second surface 18 opposite to the first surface 16, and defines a width or thickness between the first surface 16 and the second surface 18. The nanoparticles 14 have been deposited into the substrate through the first surface 16. As shown, the nanoparticles 14 penetrate through the first surface 16 into the "depth" of the substrate 10 between the first surface 16 and the second surface 18. In some embodiments, the nanoparticles 14 penetrate from the first surface to at least 25% of the width or thickness between the first surface 16 and the second surface 18, or more preferably penetrate to at least about 50% of the thickness. In other embodiments, the nanoparticles 14 penetrate substantially throughout the substrate 10 from the first surface 16 to the second surface 18.
[0093] Nanoparticles 14 preferably include individual nanoparticles (e.g., nanoparticles that have been broken up, separated, and isolated from one another prior to being dispersed into substrate 10. Fig. 24B As shown in FIG. 1 , the nanoparticles 14 are not present in the fiber product in the layer, and there are no obvious nanofiber bundles or clusters (such as Fig.24A This allows for greater dispersion of the nanoparticles throughout the substrate, which in certain applications (e.g., gas filters) provides a more efficient filtration capability to remove pollutants. In addition, this provides a fiber material with a greater nanoparticle surface density (grams per square meter (gsm)) or "addition amount" within the material. The term "addition amount" is used herein to refer to the surface density (gsm) of a material, fiber, or particle in a thin layer, sheet, or film of the material.
[0094] In certain embodiments, the nanoparticles may include an addition amount of about 0.1 g / m2 to about 20 g / m2, preferably at least about 2.0 g / m2. The specific addition amount or surface density may depend on the application. For example, the applicant has found that a higher surface density or addition amount will increase the efficiency of the fibrous material in filtering out pollutants. Therefore, the specific nanoparticle addition amount may depend on the desired efficiency of the filter medium.
[0095] Figure 2 A fibrous material or substrate 20 is shown that includes a plurality of fibers 12 and nanoparticles 14. As shown, the nanoparticles 14 penetrate the entire width of the substrate 20 from the first surface 16 to the second surface 18. In some embodiments, the nanoparticles 14 are substantially dispersed in all of the fibers 12 of the substrate, such as Figure 2 In some embodiments, the density of nanoparticles located at the first surface 16 differs by less than 50% from the density of nanoparticles dispersed in the central portion of the substrate 20 between the surfaces 16 and 18. In some embodiments, the difference is less than 25%, preferably less than 10%. In some embodiments, the amount or number of individual nanoparticles dispersed in the central portion of the substrate 20 is at least about 50%, preferably at least about 75%, and more preferably at least about 90% of the amount of individual nanoparticles dispersed at or near the first surface 16.
[0096] In other embodiments, the nanoparticles 14 are arranged in a density gradient from the first surface 16 to the second surface 18. For example, Figure 3 A substrate 30 is shown in which the nanoparticles 14 form a density gradient, with the density of the nanoparticles 14 near the first surface 16 being higher than at the second surface 18. In some embodiments, the density of the nanoparticles located at the first surface 16 differs from the density of the nanoparticles dispersed at the second surface 18 by more than about 75%. In some embodiments, the difference is greater than 50%. In some embodiments, the difference is greater than 25%. In some embodiments, the amount or number of individual nanoparticles dispersed at or near the second surface 18 is less than about 50%, preferably less than about 25%, and more preferably less than about 10% of the amount of individual nanoparticles dispersed at or near the first surface 16.
[0097] Figure 3 The density gradient shown is substantially linear from the first surface 16 to the second surface 18. Alternatively, the density of the nanoparticles 14 may decrease in a series of discrete steps from the first surface 16 to the second surface 18, or the gradient may be random (i.e., the decrease in density is not substantially linear or step-like).
[0098] In other embodiments, nanoparticles may be added to the substrate from the first surface 16 and the second surface 18. In these embodiments, the surface density or "addition amount" at the first surface 16 and the second surface 18 may be substantially equal to each other, or they may be different depending on the application. In these embodiments, the surface density or "addition amount" in the middle of the substrate is lower than at the surfaces 16, 18. For example, the surface density in the middle of the substrate may be about 75% of the surface density at the surfaces 16, 18, or may be about 50%, 40%, or 25%.
[0099] The distribution of nanoparticles through the thickness of the fiber material can be measured, for example, using imaging techniques. Using electron microscopy or other techniques, a magnified image of the fiber product obtained in a horizontal cross section through the middle of the product thickness can be compared with an image obtained at the top or bottom surface of the product, or all three images can be compared to determine the extent to which the amount of deposited nanoparticles varies. Computerized image analysis processing can be used. For example, in Figure 3 In the embodiment of the present invention, a cross section can be taken at line AA, and a cross section can be taken at line BB. A top view of each cross section can be taken by an electron microscope, a scanning electron microscope, and other microscopes. For example, a top view of a cross section taken at section AA can be compared with a top view taken at section BB. The number of microfibers, the number of nanoparticles, or both in samples of the same two-dimensional size can be evaluated and compared. In addition, imaging techniques can be used for three-dimensional samples. These techniques can be used to evaluate the orientation and other characteristics of the fibers. These techniques can be used to determine that the nanoparticles have been deposited deep into the substrate, have been substantially deposited in most of the substrate, substantially deposited in the entire depth of the substrate, or deposited in a portion of the depth of the substrate.
[0100] The contemplated substrate fibers may be made by any method including, but not limited to, air laying, spinneret, gel spinning, melt spinning, wet spinning, dry spinning, islands in the sea staple or spunbond, cut wafer staple or spunbond, and the like. Such methods are described in U.S. Pat. Nos. 4,406,950, 6,338,814, 6,616,435, 6,861,142, 7,252,493, 7,300,272, 7,309,430, 7,422,071, 7,431,869, 7,504,348, 7,774,077, 9,522,357, 9,993,761, and U.S. Patent Publication No. 2009 / 266,759, the entire disclosures of which are incorporated herein by reference for all purposes.
[0101] The contemplated fibers may have a variety of cross-sectional shapes, including but not limited to round, bean-shaped, dog-bone-shaped, trilobal, barbell-shaped, bow-tie-shaped, star-shaped, and Y-shaped, etc. These shapes and / or other conventional shapes may be used in conjunction with the embodiments to obtain the desired performance characteristics. The fibers in the substrate are held connected to each other by thermal bonding, chemical bonding, by entanglement with each other, by use of a binder (e.g., adhesive), etc.
[0102] The fibers may be man-made or natural fibers. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high density polyethylene ("HDPE"), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polytetrafluoroethylene, polystyrene, styrene maleic anhydride, polymethylpentene, cycloolefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers (e.g., P(VDF-TrFE)) or terpolymers (e.g., P(VDF-TrF Fibers of the invention include, but are not limited to, nylon and polyamides, polymethacrylic acid, polymethyl methacrylate, polyoxymethylene, polysulfones, acrylic acid, styrenated acrylic acid, preoxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene-vinyl acetate, styrene-butadiene copolymers, ethylene / vinyl chloride copolymers, vinyl acetate copolymers, latex, polyester copolymers, carboxylated styrene acrylic acid or vinyl acetate, epoxy resins, acrylic multipolymers, phenolic resins, polyurethanes, cellulose, styrene, or any combination thereof. Other conventional fiber materials are also contemplated.
[0103] The fibers can include fibers of different sizes, with the diameters of the fibers typically ranging from about 1 micron to about 1000 microns and lengths ranging from about 1 / 2 inch to 3 inches. The fibers can be configured as a gradient density media, wherein the pore size decreases from the upper surface (upstream) to the lower surface (downstream) of the filter to improve capture efficiency and dust collection capabilities. This configuration also allows different amounts of nanoparticles to be dispersed to different depths in the filter medium. For example, the upstream side of the filter medium can have the largest fiber size to allow for larger void spaces and a larger density of nanoparticles, while the downstream side of the filter medium has smaller sized fibers to provide a lower density of nanoparticles. Alternatively, this structure can be reversed to provide a larger density of nanoparticles within the downstream portion of the filter medium.
[0104] The fibers in the media may be held connected to other fibers by thermal bonding, chemical bonding, or entanglement with each other. Bicomponent fibers may be used, especially in the case of mechanical filtration, and are formed by extruding two polymers from the same spinneret, containing the two polymers in the same filament. Suitable materials for bicomponent fibers include, but are not limited to, polypropylene (PP) / polyethylene (PE) and polyethylene terephthalate (PET) / polypropylene (PP), etc.
[0105] In some embodiments, the substrate can include a "high loft" fiber material that includes spunbond or air-through bonded combed fibrous fibers. The term "high loft" as used herein refers to a volume of void space that is greater than the volume of the entire solid. In air-through bonded combed nonwoven fibers, the bulkiness of the substrate can be controlled by various methods known to those skilled in the art. For example, the bulkiness can be increased by applying less pressure to the medium during bonding. In another example, a high loft nonwoven material can be made with fibers having a greater thickness, such as a thickness greater than 3 denier, such as 5 denier or greater, 6 denier or greater (discussed in more detail below). In other embodiments, the bulkiness can be increased by using non-concentric biocomponent fibers, such as Figure 5C shown in FIG. 1 and discussed in more detail below.
[0106] In certain embodiments, the fiber may include a silicone-based coating to improve the efficiency of the filter media in capturing pollutants, especially pollutants within the E2 and E3 particle groups. The silicone-based coating may include a reactive silicone crude emulsion. The silicone emulsion may, for example, include a dimethylsiloxane emulsion, an amino-type silicone emulsion, an organofunctional silicone emulsion, a resin-type silicone emulsion, or a film-forming silicone emulsion, etc. In one embodiment, the reactive silicone crude emulsion contains amino-functional polydimethylsiloxane and / or polyethylene glycol monotridecyl ether. Suitable silicone coatings are described in U.S. Provisional Patent Application No. 63 / 406,686, jointly assigned, filed on September 14, 2022, the entire disclosure of which is incorporated herein by reference.
[0107] The filter media may contain a charge additive to modify the triboelectric charge of the fibers and increase the stability and / or duration of the triboelectric charge in the filter. This improves the overall filtration efficiency of the filter without compromising other important properties of the filter, such as life, dust collection capacity, and pressure drop or airflow through the filter. Suitable charge additives for triboelectric charging are described in commonly assigned Provisional Patent Application No. 63 / 410,731, filed on September 28, 2022, the entire disclosure of which is incorporated herein by reference for all purposes.
[0108] Fiber can have the thickness suitable for application.In some embodiments, fiber has at least one size in the range of about 1 micron to about 10000 microns or in the range of about 1 micron to about 1000 microns or in the range of about 10 to 100 microns.The thickness of fiber can also be measured by denier, and denier is the measurement unit of the linear mass density of fiber.In some embodiments, fiber can have the linear density of about 1 denier to about 10 deniers.Nanoparticle is to have at least one size in the range of about 1 nanometer to about 1000 nanometers or in the range of about 1 nanometer to about 100 nanometers.The size of above-mentioned fiber and nanoparticle can be diameter or width, and this depends on the shape of fiber or nanoparticle.
[0109] For gas filters (eg, pleated or non-pleated air filters), the linear density of the fibers may range from about 1 denier to about 10 denier. The filter media may contain fibers having the same or different linear densities.
[0110] The fibers in air filters typically have a linear density of about 3 deniers or less to ensure that the fibers are small enough to capture pollutants that pass through the filter. Applicants have surprisingly discovered that by using nanoparticles dispersed in the filter media, the fibers can have a greater linear density, such as greater than 3 deniers. This is because the nanoparticles provide significant filtering capabilities. In some cases, the fibers can have a linear density greater than 3 deniers, 5 deniers or greater, 6 deniers or greater, or up to 7-10 deniers.
[0111] Applicants have also discovered that in some applications, fibers having a greater linear density (e.g., greater than about 3 denier) than fibers used in conventional filters provide more open space or pores in the filter media, which allows a greater density of nanoparticles to be dispersed therein. Although this may be counterintuitive to one skilled in the art, Applicants have discovered that fibers having a greater linear density incorporating nanoparticles actually improve the overall efficiency of the filter.
[0112] In some embodiments, the filter medium may include at least two different fiber thicknesses or linear densities to provide at least two different filter layers in the same filter medium. For example, in some cases, a portion of the filter medium may include fibers having a linear density greater than 3 deniers, such as 5 deniers or greater, or 6 deniers or greater. Other portions of the filter medium may include fibers having a more standard linear density of 3 deniers or less. This double-layer filter medium produces a first filter portion, the first filter portion primarily utilizing nanoparticles with a high density within the larger thickness fibers to filter pollutants, and a second filter portion primarily utilizing fibers with a lower linear density to filter pollutants, although both portions may include nanoparticles dispersed throughout the fibers. In some embodiments, the filter medium may include three or more separate portions or layers, each portion having a different denier fiber range.
[0113] Figure 4 A dual-layer filter medium is shown, which includes a first substrate 40 having a first surface 42 and a second surface 44 opposite the first surface; and a second substrate 50 having a first surface 52 and a second surface 54 opposite the first surface. The second surface 44 of the substrate 40 is bonded to the second surface 54 of the first substrate in any manner known to those skilled in the art. The first substrate 40 includes fibers 46 of a relatively small linear density, such as about 3 denier or less. The second substrate 50 includes fibers 56 of a relatively large linear density, such as about 3 denier or greater, such as 5 denier, 6 denier or greater. The second substrate 50 also includes individual nanoparticles 58 dispersed throughout the fibers 56 and bonded to the fibers 56 and / or retained by the second substrate 50. The first substrate 40 may or may not include nanoparticles.
[0114] The first substrate 40 is configured to filter pollutants primarily using fibers 46, although as previously described, the first substrate 40 may also include nanoparticles. The second substrate 50 is configured to filter pollutants using fibers 56 and nanoparticles 58.
[0115] In some embodiments, the substrate may include additives such as antimicrobial and / or antiviral compositions, such as silver, zinc, copper, organosiloxanes, tributyltin, organic compounds containing chlorine compounds, bromine compounds, or fluorine compounds.
[0116] The fibers may include biocomponent fibers that include two or more different fibers bonded to each other. The fibers may comprise the same material or different materials.
[0117] Figures 5A-5C Various examples of biocomponent fibers that can be used with the nonwoven materials disclosed herein are shown. Figure 5AA fiber 60 is shown having a core fiber 62 and a surrounding sheath fiber 64. In this embodiment, the core 62 is substantially concentric with the sheath. Figure 5B A biocomponent fiber 70 is shown having a first fiber 72 and a second fiber 74 arranged side by side with one another. Figure 5C A biocomponent fiber 80 is shown having a core fiber 82 and a sheath fiber 84. In this embodiment, the core 82 is non-concentric with respect to the longitudinal axis of the sheath 84, which increases the overall loft of the biocomponent fiber. Of course, other configurations are possible. For example, the inner core may include a shape other than circular, such as a dog bone, square, triangle, or diamond, etc. Alternatively, the fiber may include multiple inner cores, or may be divided into three, four, or more quadrants.
[0118] In some embodiments, nonwoven material (that is, fiber and / or nanoparticle) can be electrostatically charged, which for example makes pollutants be captured by mechanical filtration and electrostatic filtration. The combination between fiber and nanoparticle can also be enhanced by electrostatically charging nanoparticle, fiber or both. For example, in some embodiments, fiber is electrostatically charged, thereby nanoparticle can be utilized to realize mechanical filtration, and electrostatic filtration can be realized by electret substrate simultaneously. Electrostatic or electret substrate can be the high bulk friction charged filter medium made by combing and acupuncture. In one embodiment, preferably before acupuncture, nanoparticle is deposited in substrate, and then electrostatic fiber and nanoparticle acupuncture are together.
[0119] The substrate, nanoparticles, or both may be electrostatically charged using tribocharging methods, corona discharge, electrostatic fiber spinning, hydrocharging, charging rods, or other known methods. Corona charging is suitable for charging single polymer fibers or fiber blends or fabrics. Tribocharging may be suitable for charging fibers with different electronegativity. Electrostatic fiber spinning combines the charging of polymers and the spinning of fibers into a single-step process. Suitable charge additives for tribocharging are described in commonly assigned Provisional Patent Application No. 63 / 410,731 filed on September 28, 2022, the entire disclosure of which is incorporated herein by reference for all purposes.
[0120] Nanoparticles can be selected to have different triboelectric properties relative to the fibers in order to use the triboelectric effect to enhance particle removal. With this approach, the resulting nanoparticles are formed in an electric field and are less contaminated by chemicals that may weaken the triboelectric effect. Nanoparticles can also be used with different adsorption properties or surface charge characteristics than the macrofibers, such as in oil or water filtration. This difference can be used to enhance or create a local electric field gradient within the filter media to enhance particle removal. The nanoparticles and macrofibers can have different wetting characteristics.
[0121] The nonwoven material may include a binder or bonding material, such as an adhesive or binder, to promote bonding between fibers and / or retention of nanoparticles in the substrate, so that the nanoparticles can adhere to the fibers, or be retained in the substrate by the fibers to form a stable matrix. The binder or bonding material is preferably present in a relatively small amount to bond a single nanoparticle to the fibers of the entire substrate.
[0122] The binder may comprise a variety of conventional materials, including natural materials such as starch, dextrin or guar gum, etc., or synthetic resins such as EVA, PVA, PVOH, SBR and polyglycolide, etc. In certain embodiments, a solvent-based adhesive is used, wherein bonding occurs when the solvent evaporates.
[0123] In a preferred embodiment, the binder or bonding material comprises dextrin. In another embodiment, the binder comprises a combination of various substances, such as water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzenesulfonate, laurylamine oxide and ammonium hydroxide. In yet another embodiment, the binder comprises at least one PVOH. The binder can be a solution, an emulsion, a suspension, a hot melt, a curable material, a neat material and / or a combination thereof.
[0124] In some embodiments, binder resin is used, and after the binder is coated on the substrate, the binder resin can undergo crosslinking. Adhesion (water resistance / solvent resistance) can be improved by self-crosslinking when the solvent in the binder formulation evaporates or thermal activation in the drying process. In the case of some binders, crosslinking can be completed by electromagnetic radiation of high energy wavelengths, including but not limited to radio frequency (RF), ultraviolet (UV) or electron beam. The amount of the binder can be controlled by adjusting the nozzle size of the sprayer 140 or controlling the flow rate of the binder composition. Adhesive can be applied using a nozzle, dip coating or other methods.
[0125] In some embodiments, the binder or bonding material may include a surfactant to reduce the surface or interfacial tension of the binder, thereby improving its dispersion and wetting properties, and making the binder more easily penetrate into the depths of the substrate. Suitable surfactants used with the adhesive disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agent, docusate (sodium diisooctyl sulfosuccinate), alkyl ether phosphate, benzalkonium chloride (BAC) and perfluorooctane sulfonate (PFOS) etc.
[0126] In some embodiments, the substrate comprises its own binder composition. In these embodiments, a binder or bonding material may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers, one of the components comprising an outer sheath at least partially surrounding an inner core (see Figure 5A and 5C ).
[0127] The sheath may comprise a material that is bonded to the nanoparticles. For example, the sheath may comprise a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step (discussed below), the sheath portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously.
[0128] Fig.23A is a magnified image of a nonwoven article having nanoparticles deposited therein, the fiber article being free of binder material. Fig. 23B is a magnified image of a fiber product in which the nanoparticles are attached to the fibers using a binder material consisting of dextrin and water. As shown in the figure, with the use of the binder, the nanoparticles are more evenly attached to the fibers.
[0129] exist Fig.23A and 23B In the examples of , a substrate having bicomponent microfibers is used, the substrate having an inner portion consisting of polyester and an outer portion consisting of high-density polyethylene ("HDPE") . Fig.23A A microfiber nonwoven article having a bicomponent microfiber substrate is shown, with biosoluble glass nanofibers deposited in a layer only on the surface of the substrate and the nanofibers held by electrostatic forces. Fig.23A Agglomeration of nanofibers and poor retention of nanofibers can be seen in the .Substrate can be made using meltblowing, spunbonding, or other methods described herein.
[0130] exist Fig. 23BIn the example, a binder material is used. The mixture of dextrin and water is used to spray the substrate, and nanoparticles are applied to the substrate with higher uniformity and greater nanofiber retention. In other examples, any binder material disclosed in this article can be used. In addition, biosoluble glass nanoparticles have been deposited in the depths of the substrate. In this example, the MERV grade of the bicomponent microfiber substrate itself is 4-10, which can be achieved using any method described herein. In one example, as the nanoparticles are deposited in the depths of the substrate and have static charge, the microfiber substrate with a MERV of 8 at first is used to manufacture a nonwoven product with a MERV of 13 at first. In another example, the microfiber substrate with a MERV of 6 at first is used to manufacture a nonwoven product with a MERV of 15 at first. Substrate is provided on a roll, and in a roll-to-roll continuous process, for example, in any process and method described herein, nonwoven products can be manufactured on a commercial scale. In one example, the roll-to-roll process runs at a speed of 30 feet per minute.
[0131] In certain embodiments, the nonwoven materials discussed herein can be used as part of a filtration device that captures or absorbs pollutants, such as a liquid filter, a gas filter for home and commercial air filtration, a surgical or other mask, etc. The filtration device can be a mechanical filter, an adsorption filter, a chelating filter, an ion exchange filter, a reverse osmosis filter, a surface filter, or a depth filter, etc., and can be designed to remove many different types of pollutants from air or water, etc.
[0132] In one such embodiment, nonwoven material is incorporated into an air filter for removing particles and pollutants from the air, such as HEPA filter (i.e., pleated mechanical air filter), ultraviolet filter, electrostatic filter, washable filter, media filter, glass fiber filter, pleated or non-pleated air filter, activated carbon filter, bag filter, V-type compact filter, filter sheet, flat unit filter and filter cartridge etc. Nonwoven material can comprise filter media for air filter, and can be supported by support layer, scrim layer, or can be included in other layers or materials. Applicant finds, as described herein, nanoparticles are deeply incorporated into nonwoven material and can significantly improve the efficiency of air filter, without compromising other factors, such as pressure drop (i.e., air flow) by filter. In addition, these materials improve overall dust collection capacity, thereby extending the life of filter, especially compared with the filter that only relies on or mainly relies on electrostatic effect to improve efficiency.
[0133] Conventional home and commercial air filters, such as HEPA filters, are typically rated based on the filter's ability to capture particles between approximately 0.3 and 10 microns. This rating, called the Minimum Efficiency Reporting Value, or MERV, is established by the American Society of Heating, Refrigerating, and Air-Conditioning Engineers (ASHRAE). MERV ratings range from 1-16, with higher numbers indicating greater efficiency in capturing a particular type of particle. Conventional mechanical air filters typically report a MERV rating of approximately 8 for nonwoven filter materials.
[0134] Air filters are usually rated based on their initial efficiency (i.e., the efficiency of the air filter before use) and their efficiency over time and use. The latter efficiency is usually tested through a conditioning procedure, see Appendix J of ASHRAE Standard 52.2.
[0135] The air filters provided herein have an initial MERV rating of greater than about 10 and a pressure drop of less than about 0.5 inches of water column. In some cases, the initial MERV rating is about 11 and the pressure drop is equal to or less than about 0.17 inches of water column, or the initial MERV rating is about 13 and the pressure drop is equal to or less than about 0.36 inches of water column, or the initial MERV rating is about 14 and the pressure drop is equal to or less than about 0.5 inches of water column.
[0136] The gas filters provided herein have a MERV rating of 10 or higher after conditioning in accordance with ASHRAE Standard 52.2, Appendix J. In some embodiments, the MERV rating is 13 or higher after conditioning the gas filter using ASHRAE Standard 52.2, ISO Standard 16890, or any other acceptable standard in the industry.
[0137] The MERV rating of the fibrous filter media discussed herein will vary depending on many factors, including the type and size of fibers used in the filter media, the density of the individual nanoparticles in the filter media, the width of the filter media, the number and size of pleats (if any), etc. The MERV rating can be measured on a piece of fibrous product as well as a fibrous product formed as a pleated filter media, and the pressure drop for each product can be different. Likewise, the pressure drop across the filter media also depends on many factors, including those mentioned above.
[0138] One factor that affects the MERV rating and pressure drop is the density or amount of nanoparticles added to the substrate relative to the density of the fibers in the substrate. Applicants have found that the lower the ratio of substrate density to nanoparticle density, the higher the MERV rating of the filter and the higher the pressure drop. In certain embodiments, the filter media described herein have a nanoparticle surface density of about 0.1 g / m2 to about 20 g / m2, preferably at least about 2 g / m2.
[0139] In some cases, the density of the nanoparticles will also depend on the density of the actual filter media (i.e., the density of the coarse fibers). As discussed in more detail below with reference to Table 2 below, a density ratio (substrate gsm divided by added nanoparticle gsm) of about 67 results in a pressure drop of about 0.14 inches of water column and an initial MERV rating of 10. A density ratio of about 33.4 increases the MERV rating to 10, but only results in an increase in pressure drop to about 0.17. A density ratio of about 22.3 increases the initial MERV rating to about 12, with a pressure drop of about 0.24 inches of water column.
[0140] Thus, the efficiency or MERV rating of the filter can be improved as the amount of nanoparticles added increases. In particular, the applicant has found that, for example, with an addition amount of at least 2 g / m2, a filter with a MERV rating of approximately 10 can be achieved. An addition amount of 4 g / m2 or 6 g / m2 provides a filter with a MERV rating of approximately 12 and 13, respectively. An addition amount of 10 g / m2 or more results in a filter with a MERV rating of 15 or more.
[0141] Applicants have also discovered that including fibers with greater thickness or linear density results in larger pore sizes, resulting in greater pore volumes, thereby allowing for higher densities of nanoparticles within the substrate. This results in higher MERV ratings and pressure drops (as discussed below with reference to Table 2). For example, Applicants have been able to make air filters with a MERV rating of 14 and a pressure drop of 0.5 inches of water column using 5 denier biocomponent fibers. Similarly, Applicants were able to make filters with a MERV rating of 13 and a pressure drop of only about 0.29 inches of water column using 5 denier biocomponent fibers.
[0142] exist Figure 6 An example of a pleated filter media 90 is shown in FIG. Depending on the application, the filter 90 may include approximately 0 to 10 pleats per inch. The filter media may be mounted in a cardboard or metal frame and used as an easily replaceable filter article ( Figure 7 ). This figure shows a gas filter 94 made of the fiber material described herein. As shown, the filter 94 includes a pleated fiber filter medium 96 and a support layer 98 that provides rigidity and structure to the filter medium 96.
[0143] Fig.11 A gas filter 109 made with the fibrous material described herein is shown. The gas filter 109 includes a fibrous substrate having fibers and nanoparticles dispersed throughout the depth of the substrate. The substrate is then rolled into a cylindrical, conical, or other suitable shape and can be used in applications such as gas turbine and compressor intake filters and panel filters.
[0144] Other types of filters that can be developed with the fiber materials disclosed herein include conical filter cartridges, square end cap filter cartridges, bag filters, V-compact filters, plate filters, flat cell filters, pleated or non-pleated bag filter cartridge filters, and the like.
[0145] The fiber products disclosed herein can be used for medical masks or other medical applications, such as filter elements in respirators. Medical masks are designed to protect medical staff and / or patients from microorganisms and other substances. For example, medical masks can block bacteria with a size of about 3 microns and viruses with a size of about 0.1 microns. These masks are made of multi-layer fiber materials and have earmuffs, laces or other structures for attaching the mask to the face of a person. The wire can be incorporated into at least the upper part of the mask so that at least the part conforms to the face of the person. The mask may include a rigid polymer structure designed to keep the multi-layer fiber material in front of the face of the person. In one example, the mask has three layers. The outer layer and the inner layer contain fiber materials that provide air permeability, such as spunbond polypropylene, although any material mentioned in this article can also be used. The middle layer is arranged between the inner layer and the outer layer, and includes a microfiber substrate having nanoparticles deposited in the depths of the substrate to provide an initial MERV greater than 8, preferably a MERV greater than 10, and more preferably a MERV of 13 or greater. The pressure drop through the mask is 3 to 6 mmH2O, more preferably 4 mmH2O for breathability. It is desirable for the mask to have an efficiency of about 95%. Other examples of masks have four or more layers. Multiple layers of fabric may be combined in a single mask.
[0146] In certain embodiments, the fibrous material may be contained in a film or layer that includes holes, pores, or perforations. The holes may be embossed into a pattern (e.g., circles, diamonds, hexagons, ovals, triangles, rectangles, etc.) and then stretched until holes are formed in the thinned areas created by the embossing. Such porous substrates may be formed from many polymers, such as polypropylene, polyethylene, and high-density polyethylene ("HDPE"), among others. The polymer layer may include, for example, an extruded film. Apertured films are commercially available and marketed under the trademark Polyester. The substrate is supplied in roll form and the nanofibers are deposited into the substrate via a roll-to-roll process. Figures 10A-10E Examples of apertured films that can be formed using the methods described herein are shown.
[0147] In other embodiments, the gas filter includes a filter medium and a substantially rigid support layer bonded to the filter medium. The support layer contains fibers and individual nanoparticles dispersed deep within the layer. The nanoparticles are configured to filter contaminants that pass through the support layer.
[0148] Please refer to Figure 8, the composite filter member 814 includes an internal filter substrate 812 and one or more filter support members or membrane layers 810. The support member 810 can be formed from an extruded polymer sheet, such as a polypropylene film, a high-density polyethylene film, a polylactic acid film, or a thermoplastic polymer material, such as an extrudable fluoroplastic material, in an embodiment, a perfluoroalkoxyalkane (PFA) copolymer made from comonomers polytetrafluoroethylene and perfluoroalkyl vinyl ether. However, other polymer materials may also be used, such as fluoroplastics, such as ethylene monochlorotrifluoroethylene copolymer (ECTFE); ethylene-tetrafluoroethylene copolymer (ETFE) or polyvinylidene fluoride (PVDF).
[0149] In certain embodiments, the support membrane layer 810 includes individual nanoparticles, as described above, dispersed deep within the membrane layer 810. The nanoparticles allow the support membrane to filter at least some of the contaminants that pass through the filter membrane 814, i.e., in addition to the filtration provided by the internal filter substrate 812. In other embodiments, the filter substrate 812 and / or the support membrane layer 810 include such nanoparticles.
[0150] Fluoroplastic materials such as PFA are well suited for use in filters for cleaning semiconductor components and other environments where extreme cleanability and minimal potential for contamination are required. This support membrane layer is designed to both direct the flow of the fluid to be filtered along its surface and to direct the fluid through the structure into the filter substrate below to remove unwanted particles from the filtrate.
[0151] like Fig.9A and 9B As shown, the support film 810 may include a plurality of holes 828. The shape of the holes is preferably circular, but it can be appreciated that other shapes are possible, such as square, rectangular, triangular, etc. The substrate may be wound into a roll, and then unrolled and directed through a punch to form the holes 828 ( Fig.9A ). Alternatively, after the sheet is secured in place, the sheet may be directed through a punch press in a continuous operation to form a predetermined pattern of holes 828 therein.
[0152] Please refer to Fig. 9B After the holes are formed, the filter support member can be stretched in the machine direction as shown by double arrow 940 to elongate the holes 828 to provide a larger open area for the passage of fluid to be filtered by the filter media or substrate 812.
[0153] In an alternative embodiment, the support membrane 810 can be porous (i.e., having pores other than pores 828, or having pores in addition to pores 828). In this embodiment, additional fluid flow can be achieved with a substantially porous support membrane. In an exemplary embodiment, the support membrane layer has a porosity value of at least 0.5 or 50%, preferably at least 0.8 or 80%, and more preferably about 0.86 or 86%. The porosity value is defined as the non-solid body or pore volume fraction of the total volume of the material. A more complete description of this composite filter medium can be found in PCT Application No. US2020 / 040941, the entire disclosure of which is incorporated herein by reference in its entirety for all purposes.
[0154] The filter support membrane layer of the present invention can be prepared by any method known to those of ordinary skill in the art. Fig.9A and 9B In one example shown, the support film layer includes ribs. For example, the support film layer can be manufactured by extruding a polymer material to form a sheet and then passing the sheet through a nip region provided by opposing rollers; at least one of the rollers has an outer surface with countersunk grooves. The countersunk grooves in one roller are aligned with the outer surface or countersunk grooves of the other roller in the nip region to form a ribbed sheet having ribs that rise from at least one surface of the sheet. Alternatively, the ribs can be formed during an extrusion process or a known embossing method. After the ribs are formed, the support film layer can be wound into a roll, which is then unrolled and directed through a punch press to form apertures in a desired predetermined pattern along its Z direction. Alternatively, after the support film is secured in place, the support film can be directed through a punch press in a continuous operation to form a predetermined pattern of holes therein, such as Fig.9A Optionally, the machine direction (by Fig. 9B The supporting membrane layer is stretched (indicated by the double arrows in the figure) to elongate the pores, thereby providing a larger opening area for the passage of the fluid to be filtered by the filter layer or substrate.
[0155] Fig.12 The overall system 110 for manufacturing the above-mentioned fibrous materials and other products is schematically shown. As shown, the system 110 includes a feeder 120, which is used to advance a substrate 130 of fibrous fibers or other materials during the manufacturing process. The system 100 also includes a coater 140, a fiberizing system 150, and a heating and / or drying device 160. In some embodiments, the system 100 also includes a vacuum or other negative pressure source 170 below the substrate 130 and opposite to the fiberizing system 150.
[0156] In one embodiment, the feeder 120 includes a winder 122 at the downstream end of the process and an unwinder 124 at the upstream end, which unwinds the substrate 130 continuously through the system 100. In certain embodiments, the feeder 120 may also include a support surface (not shown) extending between the winders for supporting the substrate 130 as it moves downstream through the system 100. In other embodiments, the substrate is unwound directly from the unwinder 124 onto the winder 122 without additional support surfaces.
[0157] The applicator 140 is configured to spray droplets of a binder or bonding material (e.g., an adhesive or binder) onto the substrate 130 so that the nanoparticles can adhere to the fibers within the substrate 130 to form a stable matrix. The binder is preferably present in a relatively small amount to bond individual nanoparticles to the fibers throughout the substrate 130. In a preferred embodiment, the applicator 140 includes a nozzle sized to produce adhesive droplets having a diameter of approximately 20 to 30 microns to increase the penetration depth of the adhesive through the substrate 130. Of course, droplet size may be affected by many other parameters, including air pressure, air volume, air temperature, humidity, spray horn design, rheology / viscosity of the adhesive, and carrier, etc.
[0158] Of course, it should be recognized that coating the substrate with the adhesive or bonding material can be achieved using other coating methods, including ultrasonic spraying, dip coating, spin coating, gravure coating, contact roll coating, screen coating, powder coating, electrostatic, sputtering or similar coating techniques.
[0159] As described above, the binder may comprise a variety of conventional materials, including natural materials such as starch, dextrin, and guar gum, or synthetic resins such as EVA, PVA, PVOH, or SBR. In certain embodiments, a solvent-based adhesive is used, wherein bonding occurs when the solvent evaporates.
[0160] In a preferred embodiment, the binder comprises dextrin. In another embodiment, the binder comprises a combination of various substances, such as water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzenesulfonate, laurylamine oxide and ammonium hydroxide. In yet another embodiment, the binder comprises PVOH. The binder can be a solution, an emulsion, a suspension, a hot melt, a curable material, a pure material and / or a combination thereof.
[0161] In some embodiments, an adhesive resin is used, and after the adhesive is applied to the substrate 130, the adhesive resin can undergo crosslinking. Adhesion (water resistance / solvent resistance) can be improved by self-crosslinking when the solvent in the adhesive formulation evaporates or heat activation during drying. In the case of some adhesives, crosslinking can be completed by electromagnetic radiation of high energy wavelengths, including but not limited to radio frequency (RF), ultraviolet (UV) or electron beam. The amount of adhesive can be controlled by adjusting the nozzle size of the sprayer 140 or controlling the flow rate of the adhesive composition.
[0162] In some embodiments, the binder may include a surfactant to reduce the surface or interfacial tension of the binder, thereby improving its dispersion and wetting properties, and making the binder more easily penetrate into the depth of the substrate. Suitable surfactants used with the binder disclosed herein include nonionic, anionic, cationic and amphoteric surfactants, such as sodium stearate, 4-(5-dodecyl)benzenesulfonate, sodium dodecylbenzenesulfonate wetting agent, docusate (sodium diisooctyl sulfosuccinate), alkyl ether phosphate, benzalkonium chloride (BAC) and perfluorooctane sulfonate (PFOS) etc.
[0163] In some embodiments, the sprayer 140 is located upstream of the fiberizing system 150 so that the binder is sprayed before the nanoparticles are deposited. In other embodiments, the sprayer 140 is located downstream of the fiberizing system 150 so that the binder can be sprayed after the nanoparticles are deposited. In other embodiments, the system 100 includes two sprayers; one sprayer is located upstream of the fiberizing system 150 and a second sprayer (not shown) is located downstream of the fiberizing system 150 for coating the substrate 130 with a second binder after the nanoparticles are deposited.
[0164] In some embodiments, each sprayer 140 is provided with more than one nozzle head. For example, the nozzle heads can be arranged in series to achieve better uniformity or increase the fiber spray width. Alternatively, the nozzle heads can be arranged in parallel, that is, arranged across the width of the substrate to ensure that the adhesive is applied to the entire width of the substrate.
[0165] In a preferred embodiment, a negative pressure source or vacuum source (not shown) is arranged below the substrate 130 opposite the sprayer 140 to increase the penetration depth and uniformity of the adhesive. The negative pressure source can be any suitable suction device that draws the adhesive through the substrate, such as a suction pump or the like.
[0166] In some embodiments, the substrate comprises its own binder composition. In these embodiments, a binder may or may not be added to the substrate. In one such embodiment, the substrate comprises biocomponent fibers 600, one component of which comprises an outer sheath 64 at least partially surrounding an inner core 62. In certain embodiments, the sheath 64 and the core 62 may be substantially concentric with each other ( Figure 5A In other embodiments, the core 84 may be non-concentric with the sheath 82 ( Figure 5C In other embodiments, the core 72 and the sheath 74 may be arranged side by side with each other ( Figure 5B ). Of course, other configurations are possible. For example, the core 184 may include a shape other than a circle, such as a dog bone, square, triangle, or diamond, etc. Alternatively, the fiber 180 may include multiple cores, or may be divided into three, four, or more quadrants.
[0167] The sheath 64 may include a material that is bonded to the nanoparticles. For example, the sheath 64 may include a material that becomes sticky and / or flows when heated and / or dried. During the heating / drying step, the sheath 64 portion of the fiber is heated to its melting point until it becomes sticky and / or flows to bond the nanoparticles to the substrate. In a preferred embodiment, bonding and drying are performed simultaneously in the drying device 160.
[0168] Fig.13 Schematically illustrated is a fiberizing system 150 for converting a group of nanofibers into individual nanoparticles. The term "fiberizing" as used herein refers to converting (e.g., opening, separating, dividing and / or individualizing) clusters, bundles, or other groups of nanoparticles that may or may not be entangled with one another into individual nanoparticles having at least one dimension less than 1 micron. Figures 14A-14C shows entangled large nanofiber clusters ( Fig.14A ), tangled clusters of small nanofibers ( Fig. 14B ) and single nanoparticles ( Fig. 14C ) instance.
[0169] As shown, the fiberizing system 150 includes a feeder 200, such as a hopper, for feeding larger or macroscopic nanoparticle clusters / bundles (see Fig.14A ) is introduced into the system 150. The feeder 200 may include any suitable hopper device known to those skilled in the art, and is preferably configured to introduce large clusters of particles into the process at a specific rate, depending on the fiberization rate downstream. The nanoparticles may be introduced continuously at a specific rate, or intermittently at a specific rate. The large clusters of bundled nanoparticles may be broken up before being introduced into the feeder 200.
[0170] It should be appreciated that the nanoparticles can be introduced into the fiberizing device 150 in many different forms. For example, raw nanofibers can be manufactured as long separate fibers. In this form, the nanofibers can be cut to obtain the desired aspect ratio.
[0171] The system 150 further includes a separator 210, such as a stirrer, for separating or breaking large clusters / clumps of nanoparticles into smaller clusters / clumps of nanoparticles (see Fig. 14B ). The feeder 200 transfers the nanofibers to the separator 210 in a stable and continuous state by any mechanical means. The speed of the transfer will depend on a variety of factors, such as the speed at which the substrate 130 travels along the feeder 120, the fiberization rate of the nanoparticles, etc. By controlling the amount of nanoparticles falling into the separator 210, the amount of nanoparticles dispersed into the substrate can be controlled to produce a continuous manufacturing process.
[0172] In one embodiment, the separator 210 includes a housing 212 having a first opening 214 coupled to the feeder 200 and a second opening 216 coupled to the downstream process. The size of the second opening 216 preferably allows only nanofiber clusters of a specific size to pass through. The separator 210 may include a plurality of rotatable blades (not shown) designed to rotate around a vertical axis within the housing 212 to separate and open the coarse nanofiber clusters. The blades may have the same or different pitches and curvatures to allow the entangled fibers to be sequentially broken or "opened" when passing from the first opening 214 to the second opening 216.
[0173] The fiberizing system 150 also includes an air flow (discussed in more detail below) that passes through the entire system from the separator 210 to the nozzle 220. The air flow (and a series of pumps as described below) provide the motive force for moving the nanofibers through the system 150. In one embodiment, the air flow is generated by an air compressor 230 that is configured to supply compressed air to the system, although it should be appreciated that other forms of gas may be used to convey the nanofibers through the system 150.
[0174] The system 150 includes one or more pumps for moving the nanofiber clusters and ultimately moving the individual nanoparticles through the entire system. The pumps may include any suitable pumps, such as volumetric pumps, centrifugal pumps, and axial flow pumps, etc. In one embodiment, the first pump 240 includes a first inlet fluidly coupled to the air compressor 230 through a first channel 242 and a second inlet fluidly coupled to the separator 210 through a second channel 244. Compressed air is sucked into the first pump 240, which generates a negative pressure (e.g., a vacuum) to draw the nanofiber clusters from the separator 210 into the pump (discussed in more detail below). The system 150 may also include a second pump 250 and a third pump 260, each of which is fluidly coupled to the outlet of the first pump 240. The second pump 250 and the third pump 260 generate negative pressure in a similar manner, which draws the nanofiber clusters through the third channel 252.
[0175] In certain embodiments, the pump 240 includes an ejector 300. Fig.15 As shown, each ejector 300 includes a motive fluid inlet 302 and a nanofiber inlet 304, which is coupled to an outlet 306 through a fluid channel 308. The fluid channel 308 includes a converging inlet nozzle 310, a diffuser throat 312, and a diverging outlet diffuser 314. High-pressure, low-speed air is converted into low-pressure, high-speed air, thereby generating the pressure difference required to form suction. Based on the Venturi effect and Bernoulli's principle, the primary fluid medium (e.g., compressed air) is used to generate a vacuum to draw the nanofibers into the ejector 300 and discharge them through the outlet 306. The diameter of the ejector 300 depends on the volume flow rate of the compressed air, the suction requirements, the pressure drop, and the fluid pressure of the compressed air.
[0176] Please refer again Fig.13 , the third channel 252 includes a joint 254 that divides the third channel 252 into two independent channels, each channel leading to the second pump 250 and the third pump 260. The joint 254 preferably includes a surface or wall arranged substantially perpendicular to the third channel 252 to form a T-shaped intersection. The surface can be any surface that hinders the flow of nanofibers through the channel, such as the inner wall of the channel at the junction, or other changes in the direction of the inner wall, such as a curved surface or a vertical surface. Alternatively, the channel may include a wall or other surface arranged in the channel or protruding into the channel in the fluid path. In one embodiment, the channel extends to a roughly T-shaped joint that includes two independent channels extending from the joint. The second ejector is configured to draw the nanofibers into the T-joint at a speed sufficient to separate at least some of the nanofibers.
[0177] As the nanofiber clusters move through the third channel 252, they are pushed toward the surface or wall by the negative pressure applied by the second pump 250 and the third pump 260. The speed at which the nanofibers press against the joint 254 creates a collision with sufficient kinetic energy to break at least some of the nanofiber clusters into smaller nanofiber clusters and / or individual nanoparticles having at least one dimension less than 1 micron.
[0178] To generate the kinetic energy required to break up the nanofiber clusters, air is propelled through the system 150 at a velocity of about 500 feet per minute (fpm) to about 10,000 feet per minute, preferably about 2,000 fpm to about 6,000 fpm. The system 150 includes a sufficient amount of suction pressure, preferably at least about 20 psi. The suction pressure generates a total pressure of at least about 100 psi throughout the system.
[0179] In certain embodiments, the system 150 further includes a fourth fluid channel 262 and a fifth fluid channel 264 connecting the outlets of the second pump 250 and the third pump 260 to the reactor 270. Fig.16 As shown, the reactor 270 includes a top surface 272, a bottom surface 274 and an inner annular chamber 276 extending from the top surface 272 to the bottom surface 274. The reactor 270 also includes a central tube 275, which has an open upper inlet 278 and an outlet 280. The reactor 270 may also include one or more upper outlets 282. The reactor 270 may be coupled to an energy source (not shown) configured to generate a vortex of vortex gas in the annular chamber 276. The energy source may include any appropriate energy source, such as a pump, a compressor, and a generator. The vortex gas preferably flows from the bottom to the top of the reactor 270 around the central tube 275 so that the nanofiber clusters and individual nanoparticles move upward from the bottom surface 275 toward the top surface 272.
[0180] In another embodiment, the vortex is generated without a separate energy source. In this embodiment, the nanofiber clusters 290 and the individual nanoparticles 292 enter the reactor 270 through the bottom inlet 284, 285, 286, 287. The inlets 284, 285, 286, 287 are tilted upward to facilitate the movement of the nanofibers and nanoparticles around the central tube 275. In a preferred embodiment, at least one or more of the inlets 284, 285, 286, 287 are angled so that the nanofibers and nanoparticles enter the reactor 270 substantially tangentially to the central tube 275. When the nanofibers and nanoparticles enter the annular chamber 276, their velocity vectors (speed and direction) generate vortices within the reactor 270, causing them to swirl around the central tube 275 and reach the upper portion of the annular chamber 276. The swirling gas preferably flows from the bottom to the top of the reactor 270 around the central tube 275 to move the nanofiber clusters and individual nanoparticles from the bottom surface 275 upward toward the top surface 272. Nanofibers 290 and nanoparticles 292 are blown from the bottom to the top of the reactor without any interruption. As the nanofiber clusters 290 pass through the reactor 270, the vortex in the annular chamber 276 can further break up (eg, open, separate and / or individualize) the nanofiber clusters.
[0181] In some embodiments, the reactor 270 may also be coupled to an energy source (not shown) configured to generate a vortex of swirling gas within the annular chamber 276. The energy source may include any suitable energy source, such as a pump, a compressor, and a generator.
[0182] The system 100 may also include another pump or negative pressure source coupled to the upper outlet 282 (see, e.g., Fig.17 ). The negative pressure draws the fibers through the outlet 282, causing the fibers 290 to leave the reactor 270. Since the individual nanoparticles 292 are much lighter than the entangled nanofibers 290 that are still gathered together, the individual nanoparticles 292 are sucked into the upper inlet 278 of the central rod 275. At the same time, the larger and heavier nanofiber clusters 290 that have not yet been broken are drawn out through the upper outlet 284. The upper outlet 284 can be coupled to another pump (not shown), or to the first pump 240. In this way, the nanofiber clusters 290 are sent through the process again to become further broken, thereby creating a secondary feed system to further break up the remaining nanofiber clusters.
[0183] The outlet 280 of the central tube 275 is coupled to the nozzle 220 (see Fig.13). Individual nanoparticles 292 are drawn into the nozzle 220 where they are dispersed onto the surface of the substrate or into the fiber stream (discussed below). The nozzle 220 may include any suitable nozzle known to those skilled in the art. In one embodiment, the nozzle 220 has multiple outlets with outer dimensions tailored to the size (i.e., area) of the substrate passing under the nozzle 220. The nozzle 220 will disperse the nanoparticles onto the substrate at a rate driven by the pressure of the entire system.
[0184] In certain embodiments, the system 100 includes more than one nozzle coupled to the outlet 280 of the reactor 270. The nozzles can be arranged on the substrate in any suitable arrangement, such as side-by-side, in series, in parallel, and the like.
[0185] It should be appreciated that pump 240 or pumps 250, 260 may feed the nanofiber / air mixture stream directly into nozzle 220 (i.e., bypassing reactor 270). In this embodiment, the pressure within the system is designed to generate sufficient kinetic energy to break or open substantially all of the nanofibers into individual nanoparticles, so that reactor 270 is not required to separate the nanoparticles from larger fiber clusters.
[0186] Now please refer to Fig.17 , another embodiment of a fiberizing system 320 will now be described. As shown, the fiberizing system 320 includes a separator 325 for separating larger or macroscopic nanofiber clusters into smaller nanofiber clusters that will pass through the system 320. A first ejector 326 is coupled to the outlet of the separator 325 for drawing the nanofibers from the separator 325 into the system 320. As described above, an air compressor (not shown) is also coupled to the ejector 326 to provide a motive fluid.
[0187] Similar to the previous embodiment, the second and third ejectors 330 and 340 are coupled to the outlet of the first ejector 326. The nanofibers are drawn through the first ejector 320 and pushed toward the surface of the T-intersection 350 to break at least some of the nanofibers into smaller clusters or individual nanoparticles.
[0188] Each of the second ejector 330 and the third ejector 340 has an outlet coupled to another T-shaped intersection 360, 370. As described above, the nanofibers are pushed toward the surface of the T-shaped intersection 360, 370 to further break them up. The T-shaped intersections 360, 370 are each coupled to two fluid channels that enter the bottom 380 of the reactor. Therefore, the bottom 380 of the reactor has four independent inlets 382, 384, 386, 388 for the nanofibers to pass through. Each of these inlets is preferably tilted upward and located at the diagonal corner of the reactor. This allows the nanofibers to enter the vortex of the reactor and then swirl upward to the upper part 390 of the reactor.
[0189] As previously referred Fig.16 As discussed, the reactor comprises an annular chamber with a central tube, which has an open upper end and a lower end coupled to a nozzle. The nanofibers that have been fully broken into individual nanoparticles flow through the open upper end and enter the central tube to be dispersed by the nozzle. The heavier nanoparticle clusters that have not yet been broken leave the reactor through one of four independent outlets 392, 394, 396, 398. As described above, ejectors 410, 420 provide motive force for extracting nanofibers from reactor 400. Outlets 392, 394 are coupled to ejector 410 by T-shaped intersections 412, and outlets 396, 398 are coupled to ejector 420 by T-shaped intersections 422, respectively. In this case, when nanofibers pass through intersections 412, 422, they flow into one channel from two channels.
[0190] The ejectors 410, 420 are each coupled to the T-shaped intersections 430, 440. As described above, the nanofibers are pushed into the T-shaped intersections 430, 440 to further break them into individual nanoparticles. Then, the T-shaped intersections 430, 440 are each coupled to the bottom 380 of the reactor 400 (through inlets 432, 434, 442, 444). This allows the nanofibers to return to the reactor 400 for further processing. This process continues for each nanofiber cluster until the nanofiber cluster is completely broken into nanoparticles and enters the nozzle through the central tube. As a final step, the individual nanofibers are air-jetted from the nozzle onto any substrate or mixed with any fiber spinning stream. In this process, the suction is up to 20psi and the pressure is up to 100psi.
[0191] In certain embodiments, the fibrosis system 150 may include a separate control system that monitors the nanofibers to determine when they have been broken into individual nanoparticles suitable for passing through a nozzle. For example, the control system may simply monitor the pressure of the entire system to ensure that enough pressure is applied to the nanofibers to break them into nanoparticles. Alternatively, the control system may include a variety of different sensors arranged in the system to detect the characteristics of the nanoparticles, such as weight or size. The sensor may be arranged in the reactor 400, for example, so that the control system may control the various parameters of the reactor 400, such as the negative pressure applied to the outlet 392,394,396,398, the speed of the eddy current passed through the annular chamber, or the pressure applied to the center tube of the nanoparticles being sucked into the nozzle.
[0192] Fig.18 Another embodiment of a system 500 for manufacturing a multilayer fibrous material is shown. As shown, the system 500 includes a first uncoiler 502 and a second uncoiler 504 and a single winder 506 for winding a first substrate 510 and a second substrate 512 downstream of the system 500. As in the previous embodiment, the system 500 may also include a support surface (not shown) for each substrate 510, 512. The first uncoiler 502 and the second uncoiler 504 are used to advance the first substrate 510 and the second substrate 512 into the process, where they are combined together and then wound toward the single winder 506, as described below.
[0193] The system 500 includes a first sprayer 520 and a second sprayer 522, each of which is located downstream of the first uncoiler 502 and the second uncoiler 504, for applying a binder to the first substrate 510 and the second substrate 512. The system 500 also includes a first fiberizing system / device 530 and a second fiberizing system / device 532 located downstream of each spray gun 520, 522. As previously described, the fiberizing devices 530, 532 generate individual nanoparticles and disperse the nanoparticles onto the substrates 510, 512.
[0194] After the nanoparticles are dispersed into the substrates 510, 512, the two substrates are joined together at the junction 540 so that they proceed downstream together. The two substrates may be bonded to each other at this point, or they may simply be laid on top of each other.
[0195] The system 500 also includes a heater / drying device, such as an infrared oven 550, located downstream of the junction 540 of the two substrates. The heating / drying device heats and dries the two substrates to bond them to each other and to bond the nanoparticles to the fibers within the substrates. For example, the substrates can be laminated to each other.
[0196] In certain embodiments, nanoparticles are dispersed into two substrates 510, 512. In such an embodiment, system 500 is designed to disperse nanoparticles through the first surface of each substrate. Then the substrates can be joined so that the first surfaces face each other. Alternatively, the first surfaces can face away from each other (that is, joining substrates at the second relative surface of each substrate). In another embodiment, the first surface of the first substrate is joined to the second surface of the second substrate.
[0197] Fig.19 A filter article 700 is shown that includes a filter medium 710 of a fibrous material that includes fibers 722 and nanoparticles 720 dispersed in at least a portion of the filter medium 710. As shown, the filter medium 710 has a first upper surface 712 and a second lower surface 714. As described above, the nanoparticles have been dispersed through the upper surface 712 so that they penetrate through the upper surface 712 and enter the depth of the filter medium 710. The filter article 700 also includes a support layer 730, which can be any suitable support layer known in the art, such as a substantially rigid polymer that provides support for the filter medium 710, or a porous membrane having a plurality of holes for gas or fluid to pass through (as described above).
[0198] Fig. 20 Another filtration article 740 is shown that includes a filter media 710 of a fibrous material including fibers 722 and nanoparticles 720 dispersed in a portion of the filter media 710. In this embodiment, the article 740 includes a scrim layer 750 bonded to a support layer 730.
[0199] Fig.21 A dual-layer filter article 760 is shown comprising a first filter medium 762 and a second filter medium 764 bonded to each other. As shown, nanoparticles 720 have been dispersed throughout the depth of each filter medium 762, 764. In this embodiment, the nanoparticles 720 are dispersed through the inner surfaces 766, 768 of the filter media 762, 764. In another embodiment (not shown), the nanoparticles are dispersed through the outer surfaces 770, 772 of the filter media 762, 764. In yet another embodiment, the nanoparticles 720 can be deposited on the inner surface 766 of the medium 762 and the outer surface 772 of the medium 764.
[0200] In another aspect, a system for making fibrous material comprises a first device for producing one or more fiber streams and a second device for separating nanoparticles in a gaseous medium. The second device disperses the nanoparticles into a stream, and the stream is sent into the fiber stream to form the fibrous material. The system may also include a dispersing device, such as a nozzle, which is coupled to the second device and is configured to feed the nanoparticles substantially uniformly into the fiber stream. The fiber stream may be produced by any suitable mechanism known in the art, such as meltblowing, spunbonding or spunlace, thermal bonding, combing, air-laid, wet-laid, extruded, co-molded, acupuncture, stitching or hydroentanglement, etc.
[0201] In one example, the system can include a spunbond line, in which filaments are formed by spinning a molten polymer and stretching the molten filaments. The fiber bundles of the filaments are separated and spread out, and then layered on a net to form a web. The fibers are bonded into the form of a sheet by thermal bonding and embossing. For example, the first stream 630 can be introduced before the attenuation zone or before the bonding (consolidation) process.
[0202] In another embodiment, the system may include two carding machines arranged in series with each other. The first stream 630 may be introduced at any point after the first carding line and before the second carding line so that the nanoparticles are sandwiched between the two carded fiber webs. Afterwards, all fibers containing nanoparticles are bonded together in a hot air bonding oven (thermal interlocking of the nanoparticles).
[0203] exist Fig. 22 Another embodiment for producing one or more fiber streams is shown in . In this embodiment, nanoparticles are dispersed between two meltblown dies, where molten polymer is pushed through small holes to produce fibers. When the nanoparticles encounter the still tacky fibers, they mechanically entangle with the fibers and thermally bond to the fibers. Therefore, in some embodiments, no additional bonding process is required.
[0204] like Fig. 22 As shown, the apparatus 600 for forming a fibrous nonwoven structure includes a fiberizing system 610 similar to one of the above-described systems and devices. The fiberizing system 610 includes a nozzle 620 or similar device for dispersing individual nanoparticles into a first stream 630. The apparatus 600 also includes a system for generating one or more fiber streams that will be combined with the stream 630 of the individual nanoparticles. The system may include any system known in the art, such as spunbonding, carding, and extrusion, etc.
[0205] In another embodiment, the device includes a first feeder and a second feeder, such as a hopper 640, 642, coupled to a first extruder 650 and a second extruder 652. For example, each extruder may include an extrusion screw (not shown) driven by a conventional drive motor (not shown). When the polymer advances through the extruders 650, 652, the extrusion screw is rotated by the drive motor, so the polymer is gradually heated to a molten state. Thermoplastic polymers are heated to a molten state and can be completed in a plurality of discrete steps, and when they advance to two melt-blown dies 660, 662 respectively by discrete heating zones of extruders 650, 652, their temperature gradually increases. Melt-blown dies 660, 662 can be another heating zone, in which the temperature of the thermoplastic resin is maintained at an elevated level for extrusion.
[0206] Each meltblowing die 660, 662 is configured so that the two attenuating gas streams of each die converge to form a single gas stream that entrains and attenuates the molten strands as they exit the small holes or orifices 672 in the meltblowing die. The molten strands 20 are attenuated into fibers or, depending on the degree of attenuation, into microfibers of small diameter, which are generally smaller than the diameter of the orifices 672. Thus, each meltblowing die 660, 662 has a corresponding single primary gas stream 680, 690 consisting of a gas containing entrained and attenuated polymer fibers.
[0207] The primary air streams 680, 690 containing polymer fibers are aligned so that they converge in the forming zone 700. In addition, a first stream 630 consisting of a single nanoparticle is added to the two primary air streams 680, 690 of thermoplastic polymer fibers or microfibers in the forming zone 30. The introduction of the single nanoparticle into the two primary air streams 680, 690 of fibers is designed to produce a distribution of secondary fibrous material 32 within the combined primary air streams 680, 690 of fibers. This can be achieved by merging the first stream 630 consisting of a single nanofiber between the two primary air streams 680, 690, which causes all three air streams to converge in a controlled manner.
[0208] Examples of suitable meltblowing dies that can be used to make nonwoven materials are discussed in more detail in U.S. Patent Nos. 6,972,104, 8017534, and 7772456, and U.S. Patent Application No. US20200216979A1, the entire disclosures of which are incorporated herein by reference in their entirety.
[0209] Example 1
[0210] A microfiber substrate of bicomponent fibers is provided in roll form, having an inner circular portion composed of polyester and an outer concentric portion composed of HDPE. In a roll-to-roll process, the substrate is sprayed with an adhesive and nanofibers or nanoparticles of biosoluble glass fibers are deposited. The nonwoven article is then heated in an oven and the cooled nonwoven article is collected on another roll.
[0211] Follow the steps below Figure 12-16 Nanoparticles were deposited by the process described in . In the experiments, biosoluble glass nanofibers were used. The nanofibers were approximately 700 nanometers in diameter and approximately 500 micrometers in length. In the following examples, a carded hot air bonded nonwoven material made of bicomponent fibers was used as the substrate:
[0212] Flat sheet filter media samples were tested at a filtration velocity of 110 fpm. Sample dimensions were 12 inches by 12 inches. NaCl salt particles ranging from 0.3 to 10 microns were used as contaminants.
[0213] Example 2
[0214] A carded nonwoven made of 3 denier PET / PE bicomponent fibers was used as the substrate. A composition comprising water, 2-hexyloxyethanol, isopropanolamine, sodium dodecylbenzene sulfonate, laurylamine oxide, and ammonium hydroxide was used as the binder. Different nanofiber addition amounts were controlled by adjusting the line speed.
[0215] Table 1
[0216]
[0217] This example shows that by controlling the amount of nanoparticles added, the MERV rating can be increased from MERV 7 to a maximum of MERV 13.
[0218] Example 3
[0219] A high loft hot air carded nonwoven with 5 denier bicomponent fibers was used as the substrate. A typical starch binder was diluted and sprayed before nanofiber deposition. As the solvent evaporated and dried under an infrared heater, the starch fully bonded the nanofibers.
[0220] Table 2
[0221]
[0222] Example 4
[0223] Using spunbond or meltblown media as a substrate, after IPA discharge, nanoparticles are incorporated into a substrate as described herein. Spunbond fibers are made of a molten polymer that is spun and stretched to produce filaments. The average basis weight of the substrate is about 90gsm and the average thickness is about 0.57mm. A base sample without any nanoparticles is used. Four independent samples are prepared, which contain nanoparticles incorporated into a substrate as described herein. In sample 2, after IPA discharge, nanoparticles are incorporated into meltblown fibers. In samples 1, 3 and 4, after IPA discharge, nanoparticles are incorporated into spunbond fibers. The results of this test are shown in Table 3 below.
[0224] Table 3
[0225] Sample No. Substrate PD E1 E2 E3 MERV 1 CAB81(Spunbond) 0.41 96% 100% 100% 16 2 CAB81(meltblown) 0.24 75% 98% 100% 14 3 CAB81(Spunbond) 0.40 92% 100% 100% 15 4 CAB81(Spunbond) 0.17 48% 87% 99% 12 Base CAB81(Spunbond) 0.07 9% 46% 90% 9
[0226] As shown above, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was higher than the base samples, with significant improvements in the efficiency of the E2 and E3 particle groups. When nanoparticles were used, the overall MERV rating of the samples increased from MERV 7 (base samples) to MERV 12 to MERV 16. The base samples without nanoparticles had a pressure drop of 0.07 inches of water column. Samples 1-4 had a slightly increased pressure drop ranging from 0.17 to 0.41 inches of water column. In Sample 2, where nanoparticles were incorporated into the meltblown fibers, the MERV rating was 14 and the pressure drop was 0.24 inches of water column.
[0227] Example 5
[0228] A 5 denier hot air carded fiber was used as the substrate. A base sample without nanoparticles was used. Two separate samples were prepared containing nanoparticles incorporated into a substrate as described herein. The results of this test are shown in Table 4 below.
[0229] Table 4
[0230] Sample No. Substrate PD E1 E2 E3 MERV Base 5D fiber combing 0.03 -1% 2% 38% 6 1 5D fiber combing 0.31 57% 90% 98% 13 2 5D fiber combing 0.33 61% 92% 98% 13
[0231] As shown above, in all three particle groups, the efficiency of the filter media samples incorporating nanoparticles was significantly higher than the base samples. When nanoparticles were used, the overall MERV rating of the samples increased from MERV 6 (base sample) to MERV 13. The base sample without nanoparticles had a pressure drop of 0.03 inches of water column. Sample 1 had a slightly increased pressure drop ranging from 0.31 to 0.33 inches of water column.
[0232] Example 6
[0233] Meltblown fibers were used as substrates. The average basis weight of the substrate was about 24 gsm and the average thickness was about 0.4 mm. A base sample without nanoparticles or adhesives (e.g., PVOH) was used. Sample 1 contained meltblown fibers with a belt facing upward. PVOH was sprayed onto the fibers, but the nanoparticles were not incorporated therein, and sample 2 contained meltblown fibers with a fuzzy side facing upward. PVOH was sprayed onto the fibers, but the nanoparticles were not incorporated therein. Sample 3 contained meltblown fibers, on which PVOH was sprayed, and the nanoparticles were incorporated into the fibers as described herein. The results of this test are shown in Table 5 below.
[0234] Table 5
[0235] Sample No. Substrate PD E1 E2 E3 MERV Base Meltblown 0.35 82% 96% 99% 14 1 Meltblown 0.38 68% 88% 93% 13 2 Meltblown 0.41 78% 95% 97% 14 3 Meltblown 1.02 92% 99% 99% 15
[0236] As shown above, in all three particle groups, especially in the E1 particle group, the efficiency of sample 3 with nanoparticles is higher than the other three base samples. When using nanoparticles, the overall MERV rating of sample 3 is improved from MERV 13 or 14 (base samples) to MERV 15. The PVOH added to samples 2 and 3 did not significantly increase the pressure drop (i.e., 0.35 in the base sample, 0.38 and 0.41 in samples 1 and 2). The pressure drop of sample 3 increased from about 0.40 inches of water column to about 1 inch of water column. In sample 3 where nanoparticles were incorporated into the meltblown fiber, the MERV rating was 15 and the pressure drop was 1.02 inches of water column.
[0237] Example 7
[0238] 5 denier hot air combed fibers were used as the substrate. A base sample without nanoparticles was used. Seven additional samples were prepared, which contained 5 denier combed fibers with nanoparticles incorporated into the substrate as described herein. The results of this test are shown in Table 6 below.
[0239] Table 6
[0240]
[0241]
[0242] As shown above, the seven samples incorporating nanoparticles were more efficient than the base samples in all three particle groups, especially in the E2 and E3 particle groups. The overall MERV rating increased from MERV 6 (base sample) to MERV 7 to MERV 13 when nanoparticles were used. The pressure drop only increased from 0.03 inches of water column to a maximum of 0.32 inches of water column.
[0243] Example 8
[0244] High bulk spunbond fibers were used as substrates in a continuous fiber production line. This test included two different versions: 205-6 and 205-2, where the continuous fiber production line was set up differently to produce two substrates with different weights and thicknesses. For each version (205-6 and 205-2), a base sample without incorporated nanoparticles was used. Six additional samples were prepared that contained 205-6 and 205-2 fibers with nanoparticles incorporated into the substrate as described herein. The results of this test are shown in Table 7 below.
[0245] Table 7
[0246] Sample No. Substrate PD E1 E2 E3 MERV Base 205-6 0.04 0% 9% 43% 6 Base 205-2 0.04 0% 8% 37% 6 1 205-6 0.86 88% 98% 99% 15 2 205-2 0.48 79% 96% 99% 14 3 205-6 0.87 82% 97% 99% 14 4 205-2 0.42 61% 90% 98% 13 5 205-6 0.78 79% 97% 99% 14 6 205-2 0.23 44% 79% 96% 11
[0247] As shown above, in all three particle groups, the six samples incorporating nanoparticles performed significantly better than the base samples. The overall MERV rating increased from MERV 6 (base sample) to MERV 11 to MERV 14 when nanoparticles were used. The pressure drop only increased from 0.04 inches of water column to a maximum of 0.87 inches of water column. The pressure drop in the 205-2 sample only increased to a maximum of 0.48 inches of water column.
[0248] Example 9
[0249] Spunbond and meltblown fibers were used as substrates. The average basis weight of the spunbond fiber substrate was about 70 gsm, and the average basis weight of the meltblown fiber substrate was about 24 gsm. The average thickness of the substrate was about 0.75 mm. A base sample without nanoparticles was used. Five other samples were prepared, including spunbond plus meltblown fibers, in which nanoparticles were introduced into the fibers as described herein. In samples 1-3, nanoparticles were sprayed onto meltblown fibers. In samples 4 and 5, nanoparticles were sprayed onto spunbond fibers. In addition, in samples 1 and 2, the adhesive PVOH was not sprayed onto the substrate. PVOH was sprayed onto samples 3-5. The results of this test are shown in Table 8 below.
[0250] Table 8
[0251] Sample No. Substrate PD E1 E2 E3 MERV Base Spunbond+MB 0.07 2% 17% 29% 5 1 Spunbond+MB 0.41 100% 100% 100% 16 2 Spunbond+MB 0.56 100% 100% 100% 16 3 Spunbond+MB 0.26 99% 100% 100% 16 4 Spunbond+MB 0.4 100% 100% 100% 16 5 Spunbond+MB 0.17 97% 100% 100% 16
[0252] As shown above, in all three particle groups, the five samples incorporating nanoparticles performed significantly better than the base samples. The overall MERV rating increased from MERV 5 (base sample) to MERV 16 when nanoparticles were used. The pressure drop only increased from 0.07 inches of water column to a maximum of 0.56 inches of water column. In samples 3-5 (PVOH was sprayed onto the substrate), the pressure drop only increased to a maximum of 0.4 inches of water column.
[0253] Example 10
[0254] A 5 denier hot air combed glass fiber was used as the substrate. A base sample without nanoparticles was used. Three additional samples were prepared, including 5 denier combed glass fibers with nanoparticles incorporated therein. The results of this test are shown in Table 9 below.
[0255] Table 9
[0256] Sample No. Substrate PD E1 E2 E3 MERV Base 5D fiber combing 0.03 -1% 2% 38% 6 1 5D fiber combing 0.27 59% 91% 99% 13 2 5D fiber combing 0.18 45% 83% 98% 12 3 5D fiber combing 0.24 54% 89% 99% 13
[0257] As shown above, in all three particle groups, the three samples incorporating nanoparticles performed significantly better than the base samples. When nanoparticles were used, the overall MERV rating increased from MERV 6 (base sample) to MERV 12 or MERV 13. The pressure drop only increased from 0.03 inches of water column to a maximum of 0.27 inches of water column.
[0258] Embodiment 11
[0259] A fiber mixture of 5 denier and 7 denier hot air combed glass fibers was used as the substrate. The media was hot air bonded. A base sample without nanoparticles was used. 19 additional samples were prepared, which contained a fiber mixture of 5 denier and 7 denier combed glass fibers with nanoparticles incorporated therein. The results of this test are shown in Table 10 below.
[0260] Table 10
[0261]
[0262]
[0263] As shown above, in all three particle groups, all 19 samples incorporating nanoparticles performed significantly better than the base samples. When nanoparticles were used, the overall MERV rating increased from MERV 6 (base samples) to MERV 10 to MERV 13 (most samples were rated MERV 13). The pressure drop only increased from 0.03 inches of water column to a maximum of 0.31 inches of water column.
[0264] Although the apparatus, system and method are described in detail in accordance with certain preferred embodiments thereof herein, those skilled in the art will be able to make numerous modifications and variations therein. Therefore, the foregoing description should not be interpreted as being limited thereto, but rather should be interpreted as including the obvious variations described above, and only limited by the spirit and scope of the following claims.
[0265] For example, in a first aspect, a first embodiment is a method for continuously producing a fibrous material. The method includes advancing a substrate comprising a fibrous material from an upstream end to a downstream end; feeding a nanofiber group into a fluid medium, converting the nanofiber group into nanoparticles in the fluid medium, wherein the nanoparticles have at least one dimension less than 1 micron, and dispersing individual nanoparticles into the substrate between the upstream end and the downstream end to form an article.
[0266] A second embodiment is the first embodiment and further includes propelling the nanofiber cluster in the fluid medium at a velocity of about 500 to about 10,000 feet per minute (fpm).
[0267] A third embodiment is the second embodiment wherein the velocity is from about 2000 fpm to about 6000 fpm.
[0268] A fourth embodiment is any combination of the first three embodiments, wherein the nanoparticles are dispersed into the substrate at a rate of about 0.1 g / m2 to about 10 g / m2.
[0269] A fifth embodiment is the fourth embodiment, wherein the ratio is at least about 2.0 grams per square meter.
[0270] A sixth embodiment is any combination of the first five embodiments, wherein the substrate advances at a rate of about 0.05 to 1.0 m / sec.
[0271] A seventh embodiment is any combination of the first six embodiments, further comprising dispersing nanoparticles on the first surface of the substrate such that the nanoparticles penetrate at least the first surface of the substrate.
[0272] The eighth embodiment is any combination of the first seven embodiments, wherein the substrate has a thickness from a first surface to a second surface opposite the first surface, and the method further comprises dispersing the nanoparticles within at least 25% of the thickness from the first surface to the second surface in the substrate.
[0273] A ninth embodiment is the eighth embodiment, further comprising dispersing the nanoparticles within at least 50% of the thickness from the first surface to the second surface of the substrate.
[0274] A tenth embodiment is any combination of the previous nine embodiments, wherein the individual nanoparticles are incorporated substantially throughout the matrix to form a composite material.
[0275] An eleventh embodiment is any combination of the first ten embodiments, further comprising dispersing individual nanoparticles from a first surface to an opposing second surface of a substrate.
[0276] A twelfth embodiment is any combination of the previous eleven embodiments, wherein the nanoparticles form a density gradient from a first surface to an opposing second surface of the substrate.
[0277] A thirteenth embodiment is any combination of the previous twelve embodiments, further comprising mechanically separating large clusters of nanofibers into groups of nanofibers.
[0278] The fourteenth embodiment is any combination of the first thirteen embodiments, further comprising applying negative pressure to the nanofiber group to draw the nanofiber group into the compressed air flow.
[0279] The fifteenth embodiment is the fourteenth embodiment, further comprising pushing the group of nanofibers against a surface to break at least a portion of the group of nanofibers into individual nanofibers.
[0280] The sixteenth embodiment is the fifteenth embodiment, further comprising separating individual nanofibers from the group of nanofibers.
[0281] The seventeenth embodiment is the sixteenth embodiment further comprising propelling the nanofiber group and the single nanoparticle into the chamber to generate a vortex in the chamber, and applying negative pressure to the chamber to draw the nanofiber group away from the single nanoparticle.
[0282] An eighteenth embodiment is any combination of the previous seventeen embodiments, further comprising spraying the single nanoparticles onto the first surface of the substrate.
[0283] A nineteenth embodiment is any combination of the previous eighteen embodiments, further comprising applying suction to a second surface of the substrate opposite the first surface to draw the single nanoparticle through the substrate.
[0284] The twentieth embodiment is any combination of the first nineteen embodiments, further comprising applying a binder to the fiber material within the substrate.
[0285] The twenty-first embodiment is any combination of the previous twenty embodiments, further comprising heating the substrate to bond the fiber material to the individual nanoparticles.
[0286] The twenty-second embodiment is any combination of the previous twenty-one embodiments, further comprising converting the material into a filter.
[0287] In a twenty-third embodiment, a fiber material formed by the method of any combination of the first embodiment and / or the previous twenty-two embodiments is provided.
[0288] In a twenty-fourth embodiment, a filter medium formed by the method of any combination of the first embodiment and / or the previous twenty-two embodiments is provided.
[0289] In another aspect, a first embodiment is a system for continuously producing a fiber material. The system includes a conveyor for advancing a substrate containing a fiber material from an upstream end to a downstream end; a feeder for feeding a nanofiber group into a fluid medium; a fiberizing device coupled to the feeder and configured to convert the nanofiber group into nanoparticles, wherein the nanoparticles have at least one dimension less than 1 micron; and a dispersing device coupled to the fiberizing device for dispersing the nanoparticles into the substrate to form an article.
[0290] A second embodiment is the first embodiment, wherein the fiberizing device is configured to propel the group of nanofibers in the fluid medium at a velocity of about 500 feet per minute (fpm) to about 10,000 fpm.
[0291] A third embodiment is the second embodiment wherein the velocity is from about 2000 fpm to about 6000 fpm.
[0292] A fourth embodiment is any combination of the first three embodiments, wherein the nanoparticles are dispersed into the substrate at a rate of about 0.1 g / m2 to about 10 g / m2.
[0293] A fifth embodiment is any combination of the first four embodiments, wherein the ratio is at least about 2.0 g / m2.
[0294] A sixth embodiment is any combination of the first five embodiments, wherein the conveyor is configured to advance the substrate at a rate of approximately 0.05 to 1 m / sec.
[0295] A seventh embodiment is any combination of the first six embodiments, wherein the dispersing device comprises a nozzle configured to disperse the nanoparticles onto the first surface of the substrate such that the nanoparticles penetrate at least the first surface of the substrate.
[0296] An eighth embodiment is any combination of the first seven embodiments, wherein the substrate has a thickness from a first surface to a second surface opposite the first surface, wherein the nozzle disperses the nanoparticles within at least 25% of the width from the first surface to the second surface within the substrate.
[0297] A ninth embodiment is any combination of the first eight embodiments, wherein the nozzle disperses the nanoparticles within at least 50% of the thickness of the substrate from the first surface to the second surface.
[0298] The tenth embodiment is any combination of the previous nine embodiments, wherein the nanoparticles are incorporated substantially throughout the matrix to form a composite material.
[0299] An eleventh embodiment is any combination of the preceding ten embodiments, wherein the nozzle disperses individual nanoparticles from a first surface to an opposing second surface of the substrate.
[0300] A twelfth embodiment is any combination of the previous eleven embodiments, further comprising a separator coupled to the feeder and configured to mechanically separate large clusters of nanofibers into groups of nanofibers.
[0301] The thirteenth embodiment is any combination of the previous twelve embodiments, wherein the fiberizing device comprises a compressed air source and a pump, wherein the pump is configured to push the nanofiber group and the compressed air toward the surface at a speed sufficient to break at least a portion of the nanofiber group into individual nanoparticles.
[0302] The fourteenth embodiment is any combination of the previous thirteen embodiments, wherein the pump comprises an ejector configured to generate negative pressure to draw the nanofiber group from the separator.
[0303] A fifteenth embodiment is any combination of the previous fourteen embodiments, further comprising a reactor having an internal chamber fluidly coupled to a pump, wherein the reactor is configured to separate individual nanoparticles from the nanofiber clusters.
[0304] The sixteenth embodiment is any combination of the first fifteen embodiments, wherein the internal chamber of the reactor comprises one or more inlets coupled to the pump, and wherein the pump is configured to propel individual fibers and nanofiber clusters through the inlets at a velocity vector that creates a vortex within the reactor.
[0305] The seventeenth embodiment is any combination of the first sixteen embodiments, wherein the internal chamber includes one or more outlets located at the end of the internal chamber opposite to the one or more inlets, and the system also includes a second pump coupled to the outlet and configured to apply negative pressure to the chamber to draw the nanofiber group through the outlet.
[0306] An eighteenth embodiment is any combination of the previous seventeen embodiments, further comprising a coating device for dispersing the binder onto the fibrous material in the substrate.
[0307] A nineteenth embodiment is any combination of the preceding eighteen embodiments, wherein the coating device comprises a spray device having an outlet adjacent an upstream end of the feeder and a dispersion device.
[0308] The twentieth embodiment is any combination of the previous nineteen embodiments, wherein the conveyor comprises first and second opposing surfaces, wherein the substrate advances along the first surface, and wherein the system further comprises a negative pressure source adjacent the second surface.
[0309] The twenty-first embodiment is any combination of the previous twenty embodiments, further comprising a dryer disposed proximate to the conveyor between the fiberizing device and the downstream end of the feeder, the dryer for heating the nanoparticles and fibers.
[0310] The twenty-second embodiment is any combination of the previous twenty-one embodiments, wherein the article comprises a filter media.
Claims
1. A method for continuously producing a fiber material, the method comprising: advancing a substrate comprising a fibrous material from an upstream end to a downstream end; feeding the nanofiber group into a fluid medium; converting the group of nanofibers into nanoparticles in the fluid medium, wherein the nanoparticles have at least one dimension less than 1 micron; as well as Individual nanoparticles are dispersed into a substrate between an upstream end and a downstream end to form an article.
2. The method of claim 1, further comprising propelling the nanofiber cluster in the fluid medium at a velocity of about 500 to about 10,000 feet per minute (fpm).
3. The method of claim 2, wherein the velocity is from about 2000 fpm to about 6000 fpm.
4. The method of claim 1, wherein the nanoparticles are dispersed into the substrate at a rate of about 0.1 g / m2 to about 10 g / m2.
5. The method of claim 4, wherein the ratio is at least about 2.0 g / m2.
6. The method of claim 1, wherein the substrate is advanced at a speed of about 0.05 to 1.0 m / s. 7 . The method of claim 1 , further comprising dispersing the nanoparticles onto a first surface of the substrate such that the nanoparticles penetrate at least the first surface of the substrate.
8. The method of claim 1, wherein the substrate has a thickness from the first surface to a second surface opposite the first surface, the method further comprising dispersing the nanoparticles within at least 25% of the thickness from the first surface to the second surface in the substrate. 9 . The method of claim 8 , further comprising dispersing the nanoparticles within at least 50% of the thickness of the substrate from the first surface to the second surface.
10. The method of claim 1, wherein the individual nanoparticles are incorporated substantially throughout the substrate to form a composite material.
11. The method of claim 8, further comprising dispersing individual nanoparticles from the first surface to an opposing second surface of the substrate.
12. The method of claim 8, wherein the nanoparticles form a density gradient from a first surface to an opposing second surface of the substrate.
13. The method of claim 1, further comprising mechanically separating large clusters of nanofibers into groups of nanofibers.
14. The method of claim 1, further comprising applying negative pressure to the group of nanofibers to draw the group of nanofibers into a stream of compressed air.
15. The method of claim 14, further comprising pushing the group of nanofibers against a surface to break at least a portion of the group of nanofibers into individual nanofibers.
16. The method of claim 15, further comprising separating the individual nanoparticles from the group of nanofibers.
17. The method of claim 16, further comprising advancing the group of nanofibers and the single nanoparticle into a chamber to generate a vortex in the chamber, and applying negative pressure to the chamber to draw the group of nanofibers away from the single nanoparticle.
18. The method of claim 1, further comprising spraying the single nanoparticle onto the first surface of the substrate.
19. The method of claim 18, further comprising applying suction to a second surface of the substrate opposite the first surface to draw the single nanoparticle through the substrate.
20. The method of claim 1, further comprising applying a binder to the fibrous material within the substrate.
21. The method of claim 1, further comprising heating the substrate to bond the fiber material to the individual nanoparticles.
22. The method of claim 1, further comprising converting the material into a filter.
23. A fibrous material formed by the method of claim 1.
24. A filter medium formed by the method of claim 1.
25. A system for continuously producing a fiber material, the system comprising: a conveyor for advancing a substrate comprising a fibrous material from an upstream end to a downstream end; a feeder for feeding the group of nanofibers into a fluid medium; a fiberizing device coupled to the feeder and configured to convert the set of nanofibers into nanoparticles, wherein the nanoparticles have at least one dimension less than 1 micron; as well as A dispersing device coupled to the fiberizing device is configured to disperse the nanoparticles into the substrate to form an article.
26. The system of claim 25, wherein the fiberizing device is configured to propel the group of nanofibers in the fluid medium at a velocity of about 500 feet per minute (fpm) to about 10,000 fpm.
27. The system of claim 26, wherein the velocity is about 2000 fpm to about 6000 fpm.
28. The system of claim 25, wherein the nanoparticles are dispersed into the substrate at a rate of about 0.1 g / m2 to about 10 g / m2.
29. The system of claim 28, wherein the ratio is at least about 2.0 g / m2.
30. The system of claim 25, wherein the conveyor is configured to advance the substrate at a rate of approximately 0.05 to 1 m / sec.
31. The system of claim 25, wherein the dispersing device comprises a nozzle configured to disperse the nanoparticles onto the first surface of the substrate such that the nanoparticles penetrate at least the first surface of the substrate.
32. The system of claim 31, wherein the substrate has a thickness from a first surface to a second surface opposite the first surface, wherein the nozzle disperses the nanoparticles within the substrate over at least 25% of the width from the first surface to the second surface.
33. The system of claim 32, wherein the nozzle disperses the nanoparticles within at least 50% of the thickness of the substrate from the first surface to the second surface.
34. The system of claim 25, wherein the nanoparticles are incorporated substantially throughout the substrate to form a composite material.
35. The system of claim 31, wherein the nozzle disperses individual nanoparticles from a first surface of a substrate to an opposing second surface.
36. The system of claim 25, further comprising a separator coupled to the feeder and configured to mechanically separate large clusters of nanofibers into groups of nanofibers.
37. The system of claim 25, wherein the fiberizing device comprises: Compressed air source; and A pump, wherein the pump is configured to propel the group of nanofibers and compressed air toward a surface at a velocity sufficient to break at least a portion of the group of nanofibers into individual nanoparticles.
38. The system of claim 37, wherein the pump comprises an ejector configured to generate negative pressure to draw the group of nanofibers from the separator.
39. The system of claim 35, further comprising a reactor having an internal chamber fluidly coupled to the pump, wherein the reactor is configured to separate individual nanoparticles from the nanofiber clusters.
40. The system of claim 39, wherein the internal chamber of the reactor comprises one or more inlets coupled to the pump, and wherein the pump is configured to propel individual fibers and nanofiber clusters through the inlets at a velocity vector that creates a vortex within the reactor.
41. A system according to claim 40, wherein the internal chamber includes one or more outlets located at an end of the internal chamber opposite to the one or more inlets, and the system also includes a second pump, which is coupled to the outlet and configured to apply negative pressure to the chamber to draw the nanofiber group through the outlet.
42. The system of claim 25, further comprising a coating device for dispensing a binder onto the fibrous material in the substrate.
43. The system of claim 42, wherein the coating device comprises a spray device having an upstream end adjacent the feeder and an outlet of the dispersion device.
44. The system of claim 25, wherein the conveyor comprises a first surface and an opposing second surface, wherein the substrate advances along the first surface, and wherein the system further comprises a source of negative pressure adjacent the second surface.
45. The system of claim 25, further comprising a dryer disposed proximate to the conveyor between the fiberizing device and a downstream end of the feeder, the dryer for heating the nanoparticles and the fibers.
46. The system of claim 25, wherein the article comprises a filter media.
